Silicone hybrid pressure-sensitive adhesive and method for preparing same and use thereof on uneven surfaces
By using a mixed pressure-sensitive adhesive composition containing a variety of silicone compounds, the problem that silicone pressure-sensitive adhesive in the prior art is difficult to adhere to an uneven surface, and the effect of improving adhesion and physical stability while maintaining the crosslinking density is achieved.
Patent Information
- Application Number
- CN202180029693.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-07
- Filing Date
- 2021-03-02
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-03-02
AI Technical Summary
Existing silicone pressure-sensitive adhesives are difficult to adhere to uneven surfaces, and reducing crosslinking density to improve adhesion can lead to poor physical stability and non-reprocessable problems.
Provided is a silicone mixed pressure sensitive adhesive composition comprising linear or substantially linear polydiorganosiloxane, polyorganosilate resin, polyorganosiloxane, hydrosilic addition reaction catalyst, photoradical initiator, hydrosilic addition reaction inhibitor and radical scavenger.
The adhesive composition can effectively adhere to the uneven surface while maintaining sufficient crosslink density to avoid problems such as poor physical stability and non-reprocessability.
Smart Images

Figure BDA0003899215710000251 
Figure BDA0003899215710000261 
Figure BDA0003899215710000271
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 021,178, filed on May 7, 2020, under 35 U.S.C. § 119(e). U.S. Provisional Patent Application No. 63 / 021,178 is hereby incorporated herein by reference. Technical Field
[0003] The present invention relates to an organosilicon hybrid pressure-sensitive adhesive composition that is cured to form an organosilicon hybrid pressure-sensitive adhesive. The organosilicon hybrid pressure-sensitive adhesive can adhere to uneven surfaces. Background Art
[0004] Due to the elastic properties (restoring force against pressure) of conventional silicone pressure-sensitive adhesives (PSAs), it may be difficult to use conventional PSAs to cover substrates with uneven surfaces (e.g., substrates commonly found in electronic device manufacturing, which have features on their surfaces), regardless of their adhesion strength. However, reducing the crosslink density to produce a PSA with non-elastic properties (ultra-low crosslinking) to cover such uneven surfaces may result in the PSA having poor physical stability (e.g., the PSA may flow or deform under conditions of manufacturing or using electronic devices). PSAs with ultra-low crosslinking may also have the disadvantage of not being reprocessable because cohesive failure may easily occur, or have the disadvantage of not being able to tightly fix the substrate to protect the surface of the electronic device for a long time. Therefore, there is a need in the industry for a pressure-sensitive adhesive that can adhere to and conform to uneven surfaces but still has sufficient crosslinking density to overcome those disadvantages. Summary of the invention
[0005] Provided is a silicone hybrid pressure-sensitive adhesive composition and a method for preparing the same. The silicone hybrid pressure-sensitive adhesive composition comprises: (A) a linear or substantially linear polydiorganosiloxane having reactive groups including silicon-bonded aliphatic unsaturated hydrocarbon groups and silicon-bonded (meth)acryloxyalkyl functional groups in side chain positions; (B) a polyorganosilicate resin; (C) a polyorganohydrogensiloxane; (D) a hydrosilylation reaction catalyst; (E) a photoradical initiator; (F) a hydrosilylation reaction inhibitor; and (G) a radical scavenger. The silicone hybrid pressure-sensitive adhesive composition may also optionally comprise one or more of (H) a solvent, (I) an additive selected from a sensitizer and a synergist, and (J) a filler. DETAILED DESCRIPTION
[0006] The silicone hybrid pressure-sensitive adhesive composition comprises:
[0007] 100 parts by weight of (A) a linear or substantially linear polydiorganosiloxane having reactive groups which include siloxane-bonded (meth)acryloyloxyalkyl functional groups in side chain positions and optionally siloxane-bonded aliphatic unsaturated hydrocarbon groups in terminal positions, wherein the starting material (A) comprises units of the general formula M p M” q D m D' n D” o T”' r Q s , where M represents units of the formula (R 1 3SiO 1 / 2 ), M” represents units of the formula (R 1 2R 3 SiO 1 / 2 ), D represents units of the formula (R 1 2SiO 2 / 2 ), D' represents units of the formula (R 1 R 2 SiO 2 / 2 ), D” represents units of the formula (R 1 R 3 SiO 2 / 2 ), T”' represents units of the formula (R 5 SiO 3 / 2 ), and Q represents units of the formula (SiO 4 / 2 ), where each R 1 is a monovalent hydrocarbon group free of aliphatic unsaturated groups, each R 2 is a (meth)acryloyloxyalkyl functional group, each R 3 is an aliphatic unsaturated monovalent hydrocarbon group, each R 5 is independently selected from R 1 , R 2 and R 3 ; and the values of the subscripts p, q, m, n, o, r and s are such that 0 ≤ p, 0 ≤ q, o ≥ 0, the amount (p + q) ≥ 2, the amount (q + o) ≥ 2, 0 < m < 10,000, 2 < n ≤ 10,000, the amount (m + n + o) is from 100 to 10,000, the ratio (m + o) / n is from 1 / 1 to 500 / 1, the ratio (q + o) / (m + n) is from 0 to ≤ 1 / 5, 0 ≤ r ≤ 100 and 0 ≤ s ≤ 100; if 0 < r or if 0 < s, then the ratio (m + n + o) / (r + s) is from 50 / 1 to 10,000 / 1. The polydiorganosiloxane may optionally also contain small amounts of units of the formula M OH , where M OH has the formula [R 1 2(HO)SiO 1 / 2 , where R1 As mentioned above. Without wishing to be bound by theory, it is believed that a small amount of terminal M OH The residue may be present as an impurity in the starting material (A), but is not intended to be incorporated into M during the synthesis. OH , and it is not expected that the hydroxyl group will significantly affect the present application.
[0008] (B) a polyorganosilicate resin in an amount sufficient to provide a weight ratio of the polyorganosilicate resin to the (A) polydiorganosiloxane (resin / polymer ratio) of 0.15 / 1 to 4 / 1, wherein the polyorganosilicate resin comprises an average unit formula M a M” b M"' c D d D' e T'' f Q h X i , wherein M, M", D, D', T"' and Q are as described above, M"' represents the formula (R 1 2R 2 SiO 1 / 2 ) unit, where R 1 and R 2 As described above, X represents a hydroxyl group and / or an alkoxy group, and the values of the subscripts a, b, c, d, e, f, h, and i are such that a≥0, b≥0, c≥0, and the amount (a+b+c)>10 mol%; d≥0, e≥0, and the amount (d+e) is from 0 to a value sufficient to provide 30 mol% of the combined D units and D' units to the resin; f≥0, provided that the subscript f has a maximum value sufficient to provide 40 mol% of T"' units to the resin; h>0, provided that the subscript h has a value sufficient to provide 30 mol% to 70 mol% of Q units to the resin; the amount (a+b+c+d+e+f+h)=100 mol%; i≥0 is not included in the molar ratio, provided that the subscript i has a maximum value sufficient to provide 5 mol% of OX groups to the resin;
[0009] (C) a polyorganohydrogensiloxane comprising a unit formula M t M H u D v D H w T x T H y Q z , wherein M, D, T and Q represent units in the formula shown above, and M H Expression (HR 1 2SiO 1 / 2 ) unit, D H Expression (HR1 SiO 2 / 2 ) unit, T H Expression (HSiO 3 / 2 ), and the values of the subscripts t, u, v, w, x, y, and z are such that t ≥ 0, u ≥ 0, v ≥ 0, w ≥ 0, x ≥ 0, y ≥ 0, z ≥ 0, the amount (u + w + y) ≥ 2, and the amount (t + u + v + w + x + y + z) is sufficient to give the polyorganohydrogensiloxane a viscosity of 3 mPa·s to 1,000 mPa·s at 25°C;
[0010] Provided that the starting materials (A), (B) and (C) and the amounts of each are sufficient to provide:
[0011] i) > 0.2 / 1 of the silicon-bonded hydrogen atoms in the starting material (C) and the aliphatic unsaturated monovalent hydrocarbon groups R in the starting materials (A) and / or (B) 3 The molar ratio (SiH / Vi ratio),
[0012] ii) a molar ratio of silicon-bonded hydrogen atoms in the starting material (C) to reactive groups in the starting materials (A) and / or (B) (SiH / reactive group ratio) of <0.34, wherein the reactive groups are the combined R 2 and R 3 ;
[0013] (D) a hydrosilylation catalyst in an amount sufficient to provide 2 ppm to 500 ppm of platinum based on the combined weight of starting materials (A), (B) and (C);
[0014] 0.1 wt % to 10 wt % of (E) a photoradical initiator, based on the combined weight of starting materials (A), (B) and (C);
[0015] 10 ppm to 5,000 ppm of (F) a hydrosilylation reaction inhibitor, based on the combined weight of the starting materials (A), (B) and (C);
[0016] 5 ppm to 2,000 ppm of (G) a free radical scavenger, based on the combined weight of the starting materials (A) and (B);
[0017] 0 to 90 wt % of (H) a solvent, based on the combined amounts of all starting materials in the composition;
[0018] 0 to 5 wt % of (I) an additive selected from sensitizers and synergists, based on the combined weight of the starting materials (A) and (B); and
[0019] 0 wt % to 30 wt % of (J) filler, based on the combined weight of all starting materials in the composition. Also disclosed are methods for preparing silicone hybrid pressure-sensitive adhesive compositions and uses thereof.
[0020] (A) Polydiorganosiloxane having reactive groups
[0021] The silicone hybrid pressure-sensitive adhesive composition comprises 100 parts by weight of a starting material (A) linear or substantially linear polydiorganosiloxane having reactive groups including silicon-bonded aliphatic unsaturated hydrocarbon groups and silicon-bonded (meth)acryloyloxyalkyl functional groups in pendant positions. The starting material (A) comprises a unit formula M p M” q D m D' n D” o T'' r Q s , where M represents the formula (R 1 3SiO 1 / 2 ) unit, M" represents the formula (R 1 2R 3 SiO 1 / 2 ) unit, D represents the formula (R 1 2SiO 2 / 2 ) unit, D' represents the formula (R 1 R 2 SiO 2 / 2 ) unit, D" represents the formula (R 1 R 3 SiO 2 / 2 ) unit, T"' represents the formula (R 5 SiO 3 / 2 ) and Q represents the formula (SiO 4 / 2 ) units. In these units, each R 1 is a monovalent hydrocarbon group without aliphatic unsaturated groups, each R 2 is a (meth)acryloyloxyalkyl functional group, each R 3 is an aliphatic unsaturated monovalent hydrocarbon group, each R 5 Independently selected from R 1 , R 2 and R 3。And the values of the subscripts p, q, m, n, o, r, and s are such that 0 ≤ p, 0 ≤ q, 0 ≤ o, the quantity (p + q) ≥ 2, the quantity (q + o) ≥ 2, 0 < m < 10,000, 2 < n ≤ 10,000, the quantity (m + n + o) is from 100 to 10,000, the ratio (m + o) / n is from 1 / 1 to 500 / 1, the ratio (q + o) / (m + n) is from 0 to ≤ 1 / 5, 0 ≤ r ≤ 100 and 0 ≤ s ≤ 100, and if 0 < r or if 0 < s, then the ratio (m + n + o) / (r + s) is from 50 / 1 to 10,000 / 1. Alternatively, the value of the subscript o can be such that 0 < o < 10,000. Alternatively, the quantity (m + n + o) can be from 200 to 9,900. Alternatively, the quantity (m + n + o) can be from 300 to 7,000. Alternatively, the ratio (m + o) / n can be from 10 / 1 to 400 / 1. Alternatively, the ratio (m + o) / n can be from 20 / 1 to 300 / 1. Alternatively, the ratio (q + o) / (m + n) can be from 1 / 50 to ≤ 1 / 10. Alternatively, the value of the subscript r can be such that 0 ≤ r ≤ 50. Alternatively, the value of the subscript s can be such that 0 ≤ s ≤ 50. Alternatively, the ratio (m + n + o) / (r + s) can be from 100 / 1 to ≤ 5,000 / 1. Alternatively, each R 5 can be R 1 , as described above.
[0022] The quantity (q + o) can provide to the organosilicon hybrid pressure-sensitive adhesive composition a molar ratio of silicon-bonded hydrogen atoms in starting material (C) to aliphatic unsaturated monovalent hydrocarbon groups R 3 in starting material (A) sufficient to provide > 0.2 / 1 (alternatively 0.23 / 1 to 22.0 / 1, alternatively 0.23 / 1 to < 13 / 1, alternatively 0.23 / 1 to < 1 / 1) when the starting material (B) does not contain aliphatic unsaturated monovalent hydrocarbon groups R 3 of aliphatic unsaturated monovalent hydrocarbon groups R 3 content.
[0023] Suitable for R in the above units 1The monovalent hydrocarbon group (without aliphatic unsaturated groups) includes an alkyl group and an aryl group. The alkyl group can be linear, branched or cyclic. Examples of alkyl groups include methyl, ethyl, propyl (including n-propyl and / or isopropyl), butyl (including isobutyl, n-butyl, tert-butyl and / or sec-butyl), pentyl (including isopentyl, neopentyl and / or tert-pentyl); and hexyl, heptyl, octyl, nonyl and decyl, and branched saturated monovalent hydrocarbon groups with 6 or more carbon atoms; and cycloalkyl groups, such as cyclopentyl or cyclohexyl. The alkyl group may have at least one carbon atom. Alternatively, the alkyl group may have 1 to 12 carbon atoms, alternatively 1 to 10 carbon atoms, alternatively 1 to 6 carbon atoms, alternatively 1 to 4 carbon atoms, alternatively 1 to 2 carbon atoms and alternatively 1 carbon atom. Aryl groups include, alternatively, hydrocarbon groups derived from aromatic hydrocarbons by removing hydrogen atoms from cyclic carbon atoms. Examples of aryl groups include, but are not limited to, phenyl, naphthyl, benzyl, tolyl, xylyl, phenethyl, phenylpropyl, and phenylbutyl. Aryl groups have at least 5 carbon atoms. Monocyclic aryl groups may have 5 to 12 carbon atoms, alternatively 6 to 9 carbon atoms, and alternatively 6 carbon atoms. Polycyclic aryl groups may have 9 to 17 carbon atoms, alternatively 9 to 14 carbon atoms, and alternatively 9 to 12 carbon atoms. Alternatively, for R 1 , the alkyl group may be methyl, and the aryl group may be phenyl. Alternatively, each R 1 It may be an alkyl group, as described above. 1 , R 2 and R 3 The starting material (A) may contain 70 mol % or more, alternatively 80 mol % or more of R 1 . And each R 1 It may be a methyl group. Without wishing to be bound by theory, it is believed that the methyl group is non-reactive and may provide wettability to the surface of the adherend and stability (e.g., no or minimal heat shrinkage, degradation and / or discoloration) after heat treatment of the silicone hybrid pressure-sensitive adhesive (e.g., after exposure to temperatures as high as 200° C. during the (opto)electronic device manufacturing process).
[0024] R in the unit formula applicable to this article 2 The (meth)acryloxyalkyl functional groups are each independently selected from acryloxypropyl and methacryloxypropyl. 1 , R 2 and R 3 The combined meter, R 2 It may be present in a mole % range of 0.1% to 25%. Alternatively, R 2 It may be present in a mole % range of 0.8% to 12%. Alternatively, R 2 It may be present in a mole % of 1.5% to 6%.
[0025] Applicable to R 3 The aliphatic unsaturated monovalent hydrocarbon group includes alkenyl groups and alkynyl groups. The alkenyl group has a double bond and can be branched or unbranched. The alkenyl group has at least 2 carbon atoms. Alternatively, the alkenyl group may have 2 to 12 carbon atoms, alternatively 2 to 10 carbon atoms, alternatively 2 to 6 carbon atoms, alternatively 2 to 4 carbon atoms, and alternatively 2 carbon atoms. Suitable alkenyl groups include but are not limited to vinyl, allyl and hexenyl; or vinyl and hexenyl. The alkynyl group has a triple bond and can be branched or unbranched. The alkynyl group has at least 2 carbon atoms. Alternatively, the alkynyl group may have 2 to 12 carbon atoms, alternatively 2 to 10 carbon atoms, alternatively 2 to 6 carbon atoms, alternatively 2 to 4 carbon atoms, and alternatively 2 carbon atoms. The alkynyl group includes ethynyl and propynyl.
[0026] Alternatively, for R 3 Each aliphatic unsaturated monovalent hydrocarbon group is an independently selected alkenyl group, which can be selected from vinyl and hexenyl. 1 , R 2 and R 3 The starting material (A) may contain 0 mol% to 6 mol%, alternatively 0.001 mol% to 3 mol%, alternatively 0.005 mol% to 0.2 mol% of R 3 .
[0027] When the starting material (A) has a subscript p=2 and a subscript o=q=r=s=0, the starting material (A) may include a unit formula M2D m D' n , wherein the amount (m+n) is 100 to 10,000 and the ratio m / n is 1 / 1 to 500 / 1. Alternatively, the amount (m+n) may be 200 to 9,900. Alternatively, the amount (m+n) may be 300 to 7,000; and alternatively 400 to 6,000. Alternatively, the amount (m+n) may be 1,000 to 5,000. Alternatively, the ratio m / n may be 10 / 1 to 400 / 1; and alternatively 20 / 1 to 300 / 1.
[0028] The starting material (A) can be prepared by a condensation reaction or an equilibrium reaction using a (meth)acryloyl functional silane reagent with reference to "Chemistry and Technology of Silicone", Noll, Academic Press, 1968, Chapter 5, pp. 190-245. Hereinafter, the actual method for preparing polydiorganosiloxane (A) is described as follows, but is not limited to these methods. For example, polydiorganosiloxane (A) can be prepared by a one-pot synthesis method using silanol fluid, (meth)acryloyl functional dialkoxysilane and a capping agent in the presence of a trifluoromethanesulfonic acid catalyst. Heptane or toluene is used to promote the removal of methanol by azeotropic distillation. Water is also added to the reaction to ensure the complete hydrolysis of 3-methacryloyloxypropylmethyldimethoxysilane. After the reaction is completed, a neutralizing agent (such as calcium carbonate) is used to neutralize trifluoromethanesulfonic acid and filtered out after treatment. Another method can be prepared by pre-hydrolysis of (meth)acryloyl functional dialkoxysilane and subsequent condensation / disproportionation reaction involving silanol fluid and end-capping agent in the presence of phosphazene catalyst (described in U.S. Pat. No. 9,051,428 to Davio et al.). Toluene is used to reduce viscosity and facilitate removal of water / methanol by azeotropic distillation. After the reaction is completed, a neutralizing agent (such as trialkylamine and disilazane derivatives) is used to neutralize the acidic catalyst and filtered out after treatment.
[0029] Depending on the choice of the intermediate, various structures of the polydiorganosiloxane (A) can be obtained. The (meth)acryloyl functional dialkoxysilane can be selected from 3-[dimethoxy(methyl)silyl]propyl methacrylate (CAS#14513-34-9) and 3-[dimethoxy(methyl)silyl]propyl acrylate (CAS#13732-00-8). The silanol fluid can be selected from hydroxyl-terminated polydimethylsiloxane (CAS#70131-67-8), hydroxyl-terminated vinylmethylsiloxane-dimethylsiloxane copolymer (CAS#67923-19-7), hydroxyl-terminated polyvinylmethylsiloxane (CAS#68083-20-5), hydroxyl-terminated polyphenylmethylsiloxane (CAS#80801-30-5), and diphenylsilanediol (CAS#947-42-2). The end-capping agent may be selected from hexamethyldisiloxane (CAS#107-46-0), 1,3-divinyltetramethyldisiloxane (CAS#2626-95-4) and dimethylvinylsiloxy-terminated polydimethylsiloxane (CAS#68083-19-2). In addition, dialkoxysilanes or dichlorosilanes such as dimethoxydiphenylsilane (CAS#6843-66-9), dimethoxymethylvinylsilane (CAS#16753-62-1), dichlorodiphenylsilane (CAS#80-10-4), 3-mercaptopropylmethyldimethoxysilane (CAS#31001-77-1), dimethoxy(methyl)(3,3,3-trifluoropropyl)silane (CAS#358-67-8), diethoxy(methyl)phenylsilane (CAS#775-56-4), diethoxymethylsilane (CAS#2031-62-1), and dimethoxymethylsilane (CAS#16881-77-9) may be added as co-reactants. In addition, trialkoxysilanes and tetraalkoxysilanes such as trimethoxy(methyl)silane (CAS#1185-55-3), 3-(trimethoxysilyl)propyl methacrylate (CAS#2530-85-0), 3-(triethoxysilyl)propyl methacrylate (CAS#21142-29-0), tetramethyl orthosilicate (CAS#681-84-5) may be added to obtain T" and Q branched structures. Typical catalysts for condensation reactions are summarized in U.S. Pat. No. 8,076,411 to Maton et al.
[0030] Examples of polydiorganosiloxanes suitable for use as the starting material (A) include one or more of the following average composition formulas: Average Formulas Ai) to Axiv) below. In the average composition formula, the subscript after each unit represents the average number of the unit per molecule.
[0031] Ai)(ViMe2SiO 1 / 2 )2(MaMeSiO2 / 2 ) 10 (Me2SiO 2 / 2 ) 1000
[0032] Aii)(ViMe2SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 50 (Me2SiO 2 / 2 ) 2000
[0033] Aiii)(ViMe2SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 500 (Me2SiO 2 / 2 ) 6000
[0034] Aiv)(ViMe2SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 1000 (Me2SiO 2 / 2 ) 6000
[0035] Av)(ViMe2SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 50 (Me2SiO 2 / 2 ) 1990 (ViMeSiO 2 / 2 ) 200
[0036] Avi)(Me3SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 50 (Me2SiO 2 / 2 ) 1990 (ViMeSiO 2 / 2 ) 200
[0037] Avii)(Me3SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 50 (Me2SiO 2 / 2 ) 1990 (HexMeSiO 2 / 2 ) 50
[0038] Aviii)(Me3SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 50 (Me2SiO2 / 2 ) 1990 (HexMeSiO 2 / 2 ) 50
[0039] Aix)(ViMe2SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 1000 (Me2SiO 2 / 2 ) 6000 (PhMeSiO 2 / 2 ) 100
[0040] Ax)(ViMe2SiO 1 / 2 )3(MaMeSiO 2 / 2 ) 100 (Me2SiO 2 / 2 ) 1900 (MeSiO 3 / 2 )
[0041] Axi)(ViMe2SiO 1 / 2 )4(MaMeSiO 2 / 2 ) 50 (Me2SiO 2 / 2 ) 3960 (SiO 4 / 2 )
[0042] Axii)(Me3SiO 1 / 2 )3(MaMeSiO 2 / 2 ) 20 (Me2SiO 2 / 2 ) 1979 (ViMeSiO 2 / 2 ) 100 (MeSiO 3 / 2 )
[0043] Axiii)(ViMe2SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 1000 (Me2SiO 2 / 2 ) 6000 (PhPhSiO 2 / 2 ) 100
[0044] Axiv)(ViMe2SiO 1 / 2 )2(MaMeSiO 2 / 2 ) 16 (Me2SiO 2 / 2 ) 265
[0045] (B) Polyorganosilicate resin
[0046] The starting material (B) is a polyorganosilicate resin. The polyorganosilicate resin is used in the silicone hybrid pressure-sensitive adhesive composition in an amount sufficient to provide a weight ratio (resin / polymer ratio) of (B) polyorganosilicate resin to (A) polydiorganosiloxane of 0.15 / 1 to 4 / 1. Alternatively, the resin / polymer ratio may be 0.2 / 1 to 3.5 / 1. Alternatively, the resin / polymer ratio may be 0.3 / 1 to 3 / 1.
[0047] The polyorganosilicate resin comprises a unit formula M a M” b M"' c D d D' e T'' f Q h X i , wherein M, M", D, D', T"' and Q are as described above, M"' represents the formula (R 1 2R 2 SiO 1 / 2 ), X represents a hydroxyl group and / or an alkoxy group, and the values of the subscripts a, b, c, d, e, f, h, and i are such that a ≥ 0, b ≥ 0, c ≥ 0, and the amount (a + b + c) > 10 mole %; d ≥ 0, e ≥ 0, and the amount (d + e) is from 0 to a value sufficient to provide up to 30 mole % of the combined D units and D' units to the resin; f ≥ 0, provided that the subscript f has a maximum value sufficient to provide 40 mole %, alternatively 30 mole %, of T"' units to the resin; h > 0, provided that the subscript h has a maximum value sufficient to provide 30 mole % to 70 mole %, Alternatively, a value of 60 mol % of Q units; a+b+c+d+e+f+h=100 mol %; i≥0 is not included in the molar ratio, provided that subscript i has a maximum value sufficient to provide 5 mol % of hydroxyl groups to the resin. Alternatively, the amount (d+e) is from 0 to a value sufficient to provide up to 20 mol % of combined D units and D' units to the resin. Alternatively, the amount (d+e) is from 0 to a value sufficient to provide up to 10 mol % of combined D units and D' units to the resin. Alternatively, the subscript h is from 0 to a value sufficient to provide up to 15 mol % of T"' units to the resin. Alternatively, the subscript h is from 0 to a value sufficient to provide up to 8 mol % of T"' units to the resin.
[0048] Alternatively, the polyorganosilicate resin may comprise a unit formula selected from the following: M a Q h 、M a M” b Q h 、M a M” b M"' c Qh 、M a M"' c Q h 、M a D d Q h 、M a D' e Q h 、M a M” b D' e Q h 、M a M” b T'' f Q h 、M a M” b T'' f Q h , wherein subscripts a, b, and c are 20 mol% to 70 mol%, subscripts d and e are 1 mol% to 20 mol%, subscript f is 1 mol% to 25 mol%, and subscript h is 35 mol% to 65 mol%. Alternatively, subscript a may be 20 mol% to 65 mol%, subscripts b and c may be 1 mol% to 30 mol%, subscripts d and e may be 1 mol% to 20 mol%, subscript f may be 1 mol% to 25 mol%, and subscript h may be 35 mol% to 55 mol%.
[0049] Based on the resin R 1 , R 2 and R 3 The polyorganosilicate resin may contain 0 mol % to 20 mol % of R 2 , where R 1 , R 2 and R 3 As described above, the polyorganosilicate resin may contain at least 70 mol % of R 1 (Based on the R 1 , R 2 and R 3 Alternatively, based on the combined amount of R 1 , R 2 and R 3 The polyorganosilicate resin may contain 0 mol % to 15 mol % of R 2 Alternatively, the polyorganosilicate resin may contain at least 80 mol % of R 1 (Based on the R 1 , R 2 and R 3 (measured by the combined amount of the groups).
[0050] Examples of polyorganosilicate resins suitable for use as the starting material (B) include one or more of the following Bi) to Bxii).
[0051] Bi)(Me3SiO 1 / 2 ) 0.45 (SiO 4 / 2 ) 0.55
[0052] Bii)(Me3SiO 1 / 2 ) 0.50 (SiO 4 / 2 ) 0.50
[0053] Biii)(Me3SiO 1 / 2 ) 0.42 (ViMe2SiO 1 / 2 ) 0.05 (SiO 4 / 2 ) 0.53 (OH) 0.02
[0054] Biv)(Me3SiO 1 / 2 ) 0.40 (ViMe2SiO 1 / 2 ) 0.10 (SiO 4 / 2 ) 0.50
[0055] Bv)(Me3SiO 1 / 2 ) 0.42 (MaMe2SiO 2 / 2 ) 0.05 (SiO4 / 2) 0.53 (OH) 0.02
[0056] Bvi)(Me3SiO 1 / 2 ) 0.4 (MaMe2SiO 2 / 2 ) 0.2 (SiO4 / 2) 0.40
[0057] Bvii)(Me3SiO 1 / 2 ) 0.42 (MaMe2SiO 3 / 2 ) 0.05 (SiO4 / 2) 0.53
[0058] Bviii)(Me3SiO 1 / 2 ) 0.4 (MaMe2SiO 3 / 2 ) 0.2(SiO4 / 2) 0.40
[0059] Bix)(Me3SiO 1 / 2 ) 0.40 (ViMe2SiO 1 / 2 ) 0.04 (MaMeSiO 2 / 2 ) 0.02 (SiO 4 / 2 ) 0.54
[0060] Bx)(Me3SiO 1 / 2 ) 0.40 (MaSiO 1 / 2 ) 0.04 (SiO 4 / 2 ) 0.56
[0061] Bxi)(Me3SiO 1 / 2 ) 0.40 (ViMe2SiO 1 / 2 ) 0.02 (MaSiO 1 / 2 ) 0.02 (SiO 4 / 2 ) 0.56
[0062] Bxii)(Me3SiO 1 / 2 ) 0.42 (MaMe2SiO 1 / 2 ) 0.05 (SiO 4 / 2 ) 0.53
[0063] Alternatively, the polyorganosilicate resin may be selected from: Bi), Biii), Bv) and a combination of Bi), Biii) and Bv).
[0064] The polyorganosilicate resins may be prepared by any suitable method such as co-hydrolysis of the corresponding silanes or by a silica hydrosol end-capping method. The polyorganosilicate resins may be prepared by a silica hydrosol end-capping method such as those disclosed in U.S. Pat. No. 2,676,182 to Daudt et al.; U.S. Pat. No. 4,611,042 to Rivers-Farrell et al.; and U.S. Pat. No. 4,774,310 to Butler et al. The above-mentioned method of Daudt et al. involves reacting a silica hydrosol with a hydrolyzable triorganosilane (such as trimethylchlorosilane), a siloxane (such as hexamethyldisiloxane), or a mixture thereof under acidic conditions, and recovering a copolymer having M units and Q units. The resulting copolymer may contain 1 wt. % to 5 wt. % hydroxyl groups.
[0065] The intermediates used to prepare the polyorganosilicate resin may have two, three or four hydrolyzable substituents per molecule, for example, they may be diorganoalkoxysilanes, triorganoalkoxysilanes and silanes or alkali metal silicates having four hydrolyzable substituents. The intermediates may have the formula R M 2SiX 1 2 and R M SiX 1 3, where R M Selected from the above R 1 , R 2 and R 3 , and X 1 = represents a hydrolyzable substituent. A silane having four hydrolyzable substituents may have the formula SiX 2 4, where each X 2 is halogen, alkoxy or hydroxy. Suitable alkali metal silicates include sodium silicate.
[0066] The polyorganosilicate resins prepared as described above typically contain silicon-bonded hydroxyl groups, i.e., of the formula HOSi 3 / 2 , HOR M SiO 2 / 2 and / or HOR M 2SiO 1 / 2 The polyorganosilicate resin may contain up to 5% silicon-bonded hydroxyl groups. The concentration of silicon-bonded hydroxyl groups present in the polyorganosilicate resin may be determined using Fourier transform infrared (FTIR) spectroscopy according to ASTM standard E-168-16. For certain applications, it may be desirable that the amount of silicon-bonded hydroxyl groups be 2% or less, alternatively less than 0.7%, alternatively less than 0.3%, alternatively less than 1%, and alternatively 0.3% to 0.8%. The silicon-bonded hydroxyl groups formed during the preparation of the polyorganosilicate resin may be converted to triorgano (e.g., trihydrocarbyl) siloxane groups or different hydrolyzable groups by reacting the organosilicate resin with a silane, disiloxane, or disilazane containing appropriate terminal groups. The silane containing the hydrolyzable group may be added in an excess molar amount of the amount required to react with the silicon-bonded hydroxyl groups on the polyorganosilicate resin.
[0067] Alternatively, the polyorganosilicate resin may further comprise 2% or less, alternatively 0.7% or less, and alternatively 0.3% or less, and alternatively 0.3% to 0.8% of the compound represented by formula X 2 SiO 3 / 2 , X 2 R M SiO 2 / 2 and / or X 2 R M 2SiO 1 / 2 Represents a unit, where RM and X 2 As mentioned above.
[0068] Alternatively, the polyorganosilicate resin may have a terminal aliphatic unsaturated group (R 3 ). A polyorganosilicate resin having terminal aliphatic unsaturated groups can be prepared by reacting the product of Daudt et al. with an end-capping agent containing unsaturated organic groups and (optionally) an end-capping agent free of aliphatic unsaturated groups in an amount sufficient to provide 3 to 30 mole percent of unsaturated organic groups in the final product. Examples of end-capping agents include, but are not limited to, silazanes, siloxanes, and silanes. Suitable end-capping agents are known in the art and are exemplified in U.S. Patents 4,584,355; 4,591,622; and 4,585,836. A single end-capping agent or a mixture of such agents can be used to prepare such resins.
[0069] When prepared, the polyorganosilicate resin comprises the above units, and the polyorganosiloxane further comprises units having silanol (silicon-bonded hydroxyl) groups and may comprise a polyorganosiloxane of the formula Si(OSiR M 3)4 neopentamers, where R M As described above. As described in Reference Example 2 of U.S. Pat. No. 9,593,209, column 32, Si 29 Nuclear magnetic resonance (NMR) spectroscopy can be used to measure the molar ratio of M units and Q units, where the ratio is expressed as {M(resin)+(M(neopentamer)} / {Q(resin)+Q(neopentamer)} and represents the molar ratio of the total number of triorganosiloxy groups of the resin portion and the neopentamer portion of the polyorganosilicate resin to the total number of silicate groups (Q units) of the resin portion and the neopentamer portion.
[0070] The Mn of a polyorganosilicate resin depends on various factors, including the presence of M The Mn of the polyorganosilicate resin refers to the number average molecular weight measured using gel permeation chromatography (GPC) according to the procedure in Reference Example 1 of column 31 of U.S. Patent 9,593,209 when the peak representing the neopentamer is excluded from the measurement. The Mn of the polyorganosilicate resin may be 1,500 g / mol to 5,000 g / mol.
[0071] Methods for preparing (meth)acryloyloxy-functional polyorganosilicate resins suitable for use as starting material (B), such as hydrolytic or non-hydrolytic condensation or equilibration reactions of polyorganosilicate resins with (meth)acryloyloxy-functional alkoxysilanes or halosilanes under acidic or basic conditions; and similar methods for preparing organofunctional polyorganosilicates known to those skilled in the art, such as co-hydrolysis of typical organohalosilanes or organoalkoxysilanes with (meth)acryloyloxy-functional alkoxysilanes or halosilanes followed by condensation or equilibration reactions, will be described in U.S. Pat. No. 8,377,634 to Albaugh, U.S. Pat. No. 5,516,858 to Morita et al., U.S. Pat. No. 9,023,433 to Fu et al., U.S. Pat. No. 6,281,285 to Becker et al., and U.S. Pat. No. 5,010,159 to Bank et al. The (meth)acryloyloxy functional alkoxysilane or halosilane may be selected from 3-(chlorodimethylsilyl)propyl methacrylate (CAS#24636-31-5), 3-[dimethoxy(methyl)silyl]propyl methacrylate (CAS#14513-34-9), methacryloxypropylmethyldichlorosilane (CAS#18301-56-9), (3-acryloyloxypropyl)methyldichlorosilane (CAS#71550-63-5), 3-[dimethoxy(methyl)silyl]propyl acrylate (CAS#13732-00-8), 3-(Trimethoxysilyl)propyl acrylate (CAS#4369-14-6), 3-[diethoxy(methyl)silyl]propyl methacrylate (CAS#65100-04-1), 3-(trimethoxysilyl)propyl methacrylate (CAS#2530-85-0), 3-(triethoxysilyl)propyl methacrylate (CAS#21142-29-0), methacryloxypropyltrichlorosilane (CAS#7351-61-3), (3-acryloxypropyl)trichlorosilane (CAS#38595-89-0).
[0072] Another method for preparing a (meth)acryloyloxy functional polyorganosilicate resin suitable for use as starting material (B) is the hydrosilylation reaction between a hydrosilyl (-SiH) functional polyorganosilicate and a (meth)acryloyl functional olefin or alkynyl; or the hydrosilylation reaction between an alkenyl functional polyorganosilicate and a (meth)acryloyl functional hydrosilane as described in U.S. Pat. No. 4,503,208 to Lin et al., "Macromolecular Materials and Engineering", Hung-Wen et al., Vol. 292, No. 5, pp. 666-673 (2007). The (meth)acryloyl functional olefin or alkyne can be selected from allyl methacrylate (CAS#96-05-9) and propargyl acrylate (CAS#10477-47-1). The (meth)acryloyl functional hydridosilane may be selected from methacryloxypropyl tris(dimethylsiloxy)silane (CAS#17096-08-1) and 2-acrylic acid, 2-methyl-3-(1,1,3,3-tetramethyldisiloxy)propyl ester (CAS#96474-12-3).
[0073] (C) Polyorganohydrogensiloxane
[0074] The starting material (C) in the silicone hybrid pressure-sensitive adhesive composition is a compound comprising a unit of formula M t M H u D v D H w T x T H y Q z A polyorganohydrogensiloxane wherein M, D and Q represent units of the formula shown above, and M H Expression (HR 1 2SiO 1 / 2 ) unit, D H Expression (HR 1 SiO 2 / 2 ) unit, T represents the formula (R 1 SiO 3 / 2 ) unit, and T H Expression (HSiO 3 / 2) units; and the values of the subscripts t, u, v, w, x, y, and z are such that t≥0, u≥0, v≥0, w≥0, x≥0, y≥0, z≥0, the amount (u+w+y)≥3, and the amount (t+u+v+w+x+y+z) is sufficient to give the polyorganohydrogensiloxane a viscosity of 3 mPa·s to 1,000 mPa·s at 25°C, alternatively 5 mPa·s to 500 mPa·s at 25°C; and wherein R 1 As described above. Alternatively, the amount (t+u+v+w+x+y+z) may be 3 to 2,000; alternatively 3 to 1,000; and alternatively 3 to 500. Alternatively, when the subscript x=y=z=0, the polyorganohydrogensiloxane may include a unit formula M t M H u D v D H w , where the quantity (t+u)=2, and the quantity (u+w)≥3.
[0075] Examples of polyorganohydrogensiloxanes used as the starting material (C) are:
[0076] Ci) dimethylhydrogensiloxy-terminated poly(dimethylsiloxane / methylhydrogensiloxane),
[0077] Cii) dimethylhydrogensiloxy-terminated polymethylhydrogensiloxane,
[0078] Ciii) trimethylsiloxy-terminated poly(dimethylsiloxane / methylhydrogensiloxane),
[0079] Civ) trimethylsiloxy-terminated polymethylhydrogensiloxane,
[0080] Cv) a dimethylhydrogensiloxy-terminated polydimethylsiloxane, and
[0081] Cvi) A combination of two or more of Ci) to Cv).
[0082] Methods for preparing polyorganohydrogensiloxanes suitable for use as starting material (C) such as hydrolysis and condensation reactions of organohalosilanes are well known in the art. In addition, polyorganohydrogensiloxanes are known in the art and are commercially available, for example, from Dow Silicones Corporation (Midland, Michigan, USA).
[0083] The starting materials (A), (B) and (C) and the amounts of each are sufficient to provide the silicone hybrid pressure-sensitive adhesive composition with a ratio of >0.2 / 1 of the silicon-bonded hydrogen atoms in the starting material (C) to the aliphatic unsaturated monovalent hydrocarbon groups R in the starting materials (A) and / or (B). 3Alternatively, the SiH / Vi ratio may be 0.21 / 1 to 22.0 / 1; alternatively, the SiH / Vi ratio may be 0.23 / 1 to 12.5 / 1; alternatively, the SiH / Vi ratio may be 0.23 / 1 to 0.9 / 1; and alternatively, the SiH / Vi ratio may be 0.23 / 1 to 0.6 / 1.
[0084] The starting materials (A), (B) and (C) and the amounts of each are sufficient to provide the silicone hybrid pressure sensitive adhesive composition with a molar ratio of silicon-bonded hydrogen atoms in the starting material (C) to reactive groups in the starting materials (A) and / or (B) (SiH / reactive group ratio) of <0.34 / 1, wherein the reactive groups are the combined R 2 and R 3 (as defined above). The SiH / reactive group ratio is lower than the SiH / vinyl ratio. Alternatively, the SiH / reactive group ratio may be from 0.05 / 1 to 0.33 / 1; alternatively from 0.05 / 1 to 0.3 / 1; alternatively from 0.07 / 1 to 0.27 / 1; and alternatively from 0.1 / 1 to 0.25 / 1.
[0085] (D) Hydrosilylation Reaction Catalyst
[0086] The starting material (D) in the silicone hybrid pressure-sensitive adhesive composition is a hydrosilylation catalyst. The hydrosilylation catalyst includes a platinum group metal catalyst. For example, the hydrosilylation catalyst may be Di) a metal selected from platinum, rhodium, ruthenium, palladium, osmium and iridium. Alternatively, the hydrosilylation catalyst may be Dii) a compound of such a metal, such as tris(triphenylphosphine)rhodium(I) chloride (Wilkinson catalyst), a rhodium diphosphine chelate such as [1,2-bis(diphenylphosphine)ethane]dichlororhodium or [1,2-bis(diethylphosphine)ethane]dichlororhodium, chloroplatinic acid (Speier catalyst), chloroplatinic acid hexahydrate, platinum dichloride; or Diii) a complex of such a compound with a low molecular weight organopolysiloxane. Alternatively, the hydrosilylation catalyst may be Div) a compound microencapsulated in a matrix or core / shell structure. For example, complexes of platinum with low molecular weight organopolysiloxanes include complexes of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane with platinum (Karstedt catalyst). Alternatively, the hydrosilylation catalyst may be a complex of Dv) microencapsulated in a resin matrix. Exemplary hydrosilylation catalysts are described in U.S. Patents 3,159,601; 3,220,972; 3,296,291; 3,419,593; 3,516,946; 3,814,730; 3,989,668; 4,766,176; 4,784,879; 5,017,654; 5,036,117; and 5,175,325; and EP 0 347 895B. Suitable hydrosilylation catalysts are known in the art and are commercially available. For example, SYL-OFF TM 4000 Catalyst and SYL-OFF TM 2700 is commercially available from Dow Silicones Corporation (Midland, Michigan, USA).
[0087] The amount of catalyst used herein will depend on various factors, including the selection of starting materials A), B) and C) and their respective contents of aliphatic unsaturated monovalent hydrocarbon groups and silicon-bonded hydrogen atoms, and the presence or absence of inhibitors, however, the amount of catalyst is sufficient to catalyze the hydrosilylation reaction of SiH and aliphatic unsaturated monovalent hydrocarbon groups, alternatively, the amount of catalyst is sufficient to provide 1 ppm to 1000 ppm of platinum group metal based on the combined weight of all starting materials in the silicone hybrid pressure-sensitive adhesive composition; alternatively, 2 ppm to 500 ppm and alternatively 10 ppm to 100 ppm of platinum group metal based on the same basis.
[0088] (E) Photoradical initiator
[0089] The starting material (E) in the silicone hybrid pressure-sensitive adhesive composition is a photoradical initiator. Suitable photoradical initiators include UV initiators such as benzophenone derivatives, acetophenone derivatives (α-hydroxy ketones), benzoin and its alkyl esters, phosphine oxide derivatives, xanthone derivatives, oxime ester derivatives and camphorquinone. Photoradical initiators are commercially available. For example, photoradical initiators suitable for use herein include 2,6-bis(4-azidobenzylidene)cyclohexanone, 2,6-bis(4-azidobenzylidene)-4-methylcyclohexanone, 1-hydroxy-cyclohexyl-phenyl-ketone (IRGACURE TM 184), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one (IRGACURE TM 907); 2-Hydroxy-2-methyl-1-phenyl-propane-1-one (DAROCUR TM 1173); 50% IRGACURE TM 184C and 50% benzophenone mixed initiator (IRGACURE TM 500); 20% IRGACURE TM 184C and 80% DAROCUR TM 1173 mixed initiator (IRGACURE TM 1000); 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (IRGACURE TM 2959); methylbenzoyl formate (DAROCUR TM MBF); α,α-dimethoxy-α-phenylacetophenone (IRGACURE TM 651); 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone (IRGACURE TM 369); 30% IRGACURE TM 369 and 70% IRGACURE TM 651 mixed initiator (IRGACURE TM 1300); diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (IRGACURE TM TPO), (2,4,6-trimethylbenzoyl)phenylphosphinate (IRGACURE TMTPO-L), proprietary oxime ester compounds (N-1919, NCI-831, NCI-930, NCI-730 and NCI-100 supplied from Adeka Corporation), thioxanthen-9-one; 10-methylphenothiazine; isopropyl-9H-thioxanthen-9-one; 2,4-diethyl-9H-thioxanthen-9-one; 2-chlorothioxanthen-9-one; 1-chloro-4-propoxy-9H-thioxanthen-9-one; or a combination of two or more thereof. DAROCUR TM IRGACURE TM The brand of photoradical initiators is commercially available from BASF SE (Ludwigshafen, Germany). Alternatively, the photoradical initiator may be selected from: Ei) benzophenone, Eii) substituted benzophenone compounds, Eiii) acetophenone, Eiv) substituted acetophenone compounds, Ev) benzoin, Evi) alkyl esters of benzoin, Evii) substituted phosphine oxide compounds, Eviii) xanthone and Eix) substituted xanthone; and Ex) a combination of two or more of Ei) to Eix). Alternatively, the photoradical initiator may be a substituted acetophenone, such as 1-hydroxycyclohexyl phenyl ketone. The type of photoradical initiator is not particularly limited, however, some photoradical initiators, especially those containing a thioether group, a phosphinate group or a phosphine oxide group, may inhibit the hydrosilylation reaction catalyst, and therefore, when such a photoradical initiator is included, it is necessary to control the appropriate amounts of (D) the hydrosilylation reaction catalyst and (I) the additive and / or it is necessary to adjust the curing temperature / time.
[0090] The amount of photo radical initiator in the silicone hybrid pressure sensitive adhesive composition will depend on various factors including the desired reaction rate, the photoinitiator used and the selection and amount of starting materials (A) and (B) and their corresponding (meth)acryloxyalkyl group content, however, the amount may be from 0.1 wt % to 10 wt % based on the combined weight of starting materials (A), (B) and (C), alternatively from 1 wt % to 5 wt % based on the same basis.
[0091] (F) Hydrosilylation Reaction Inhibitor
[0092] The starting material (F) in the silicone hybrid pressure-sensitive adhesive composition is a hydrosilylation reaction inhibitor (inhibitor) which can optionally be used to alter the rate of reaction of the silicon-bonded hydrogen atoms of the starting materials (A), (B) and (C) with the aliphatic unsaturated hydrocarbon groups compared to the reaction rate of the same starting materials but omitting the inhibitor. Examples of inhibitors are acetylenic alcohols such as dimethyl hexynol and 3,5-dimethyl-1-hexyn-3-ol, 1-butyn-3-ol, 1-propyn-3-ol, 2-methyl-3-butyn-2-ol, 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3-phenyl-1-butyn-3-ol, 4-ethyl-1-octyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol and 1-ethynyl-1-cyclohexanol (ETCH), and combinations thereof; cycloalkenyl siloxanes such as methylvinylcyclosiloxanes, exemplified by 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetrahexenylcyclotetrasiloxane and combinations thereof; ene-yne compounds such as 3-methyl-3-pentene-1-yne, 3,5-dimethyl-3-hexene-1-yne and combinations thereof; triazoles such as benzotriazole; phosphines; thiols; hydrazines; amines such as tetramethylethylenediamine, 3-dimethylamino-1-propyne, n-methylpropargylamine, propargylamine and 1-ethynylcyclohexylamine; fumarate esters including fumarate dialkyl esters such as fumarate diethyl ester and / or fumarate dienyl esters such as fumarate diallyl ester and / or fumarate diallyloxyalkyl esters; maleates such as maleate diallyl ester and maleate diethyl ester; nitriles; ethers; carbon monoxide; olefins such as cyclooctadiene, divinyltetramethyldisiloxane; alcohols such as benzyl alcohol; and combinations thereof.
[0093] Alternatively, the inhibitor may be a silylated acetylenic compound. Without wishing to be bound by theory, it is believed that the addition of a silylated acetylenic compound reduces the yellowing of the reaction product prepared by the hydrosilylation reaction compared to the reaction product obtained by the hydrosilylation of the starting materials that do not contain a silylated acetylenic compound or contain an organic acetylenic alcohol inhibitor such as those described above.
[0094] Examples of silylated acetylenic compounds are (3-methyl-1-butyn-3-oxy)trimethylsilane, ((1,1-dimethyl-2-propynyl)oxy)trimethylsilane, bis(3-methyl-1-butyn-3-oxy)dimethylsilane, bis(3-methyl-1-butyn-3-oxy)silanemethylvinylsilane, bis((1,1-dimethyl-2-propynyl)oxy)dimethylsilane, methyl(tris(1,1-dimethyl-2-propynyloxy))silane, methyl(tris(3-methyl-1-butyn-3-oxy))silane, (3-methyl-1-butyn-3-oxy)dimethylphenylsilane, (3-methyl-1-butyn-3-oxy)dimethylhexenylsilane, (3-methyl-1-butyn-3-oxy)tris((1,1-dimethyl-2-propynyl)oxy)silane) Ethylsilane, bis(3-methyl-1-butyn-3-oxy)methyltrifluoropropylsilane, (3,5-dimethyl-1-hexyn-3-oxy)trimethylsilane, (3-phenyl-1-butyn-3-oxy)diphenylmethylsilane, (3-phenyl-1-butyn-3-oxy)dimethylphenylsilane, (3-phenyl-1-butyn-3-oxy)dimethylvinylsilane, (3-phenyl-1-butyn-3-oxy)dimethylhexenylsilane, (cyclohexyl-1-ethyn-1-oxy)dimethylhexenylsilane, (cyclohexyl-1-ethyn-1-oxy)dimethylvinylsilane, (cyclohexyl-1-ethyn-1-oxy)diphenylmethylsilane, (cyclohexyl-1-ethyn-1-oxy)trimethylsilane, and combinations thereof. Alternatively, silylated acetylenic compounds are exemplified by methyl(tris(1,1-dimethyl-2-propynyloxy))silane, ((1,1-dimethyl-2-propynyl)oxy)trimethylsilane, or combinations thereof. Silylated acetylenic compounds useful as inhibitors herein may be prepared by methods known in the art, for example, U.S. Pat. No. 6,677,740 discloses silylation of the above acetylenic alcohols by reacting the above acetylenic alcohols with chlorosilanes in the presence of an acid acceptor. Alternatively, the hydrosilylation inhibitor may be selected from: acetylenic alcohols, cycloalkenylsiloxanes, enyne compounds, triazoles, phosphines, thiols, hydrazines, amines, fumarates, maleates, nitriles, ethers, carbon monoxide, alcohols, and silylated acetylenic alcohols. Alternatively, the hydrosilylation inhibitor may be an acetylenic alcohol, such as ETCH.
[0095] The amount of inhibitor used herein will depend on various factors, including the desired reaction rate, the specific inhibitor used, and the selection and amount of starting materials (A), (B), and (C). However, when present, the amount of inhibitor may be from 10 ppm to 5,000 ppm based on the combined weight of starting materials (A), (B), and (C) in the composition. Alternatively, it may be from 20 ppm to 2,000 ppm based on the same basis.
[0096] (G) Free radical scavengers
[0097] Starting material (G) is a radical scavenger (scavenger) that can be used to control or suppress the radical reaction of the organosilicon hybrid pressure-sensitive adhesive composition. Because the organosilicon hybrid pressure-sensitive adhesive composition includes reactive (meth) acrylate groups, there can be effective radical scavengers to prevent premature reactions, such as in storage and during the use of the protective film prepared using the organosilicon hybrid pressure-sensitive adhesive composition. The scavenger comprising phenolic compounds is a class of such substances that can be used in the present invention, and these substances include, for example, 4-methoxyphenol (MEHQ, methyl ether of hydroquinone), hydroquinone, 2-methylhydroquinone, 2-tert-butylhydroquinone, tert-butylcatechol, butylated hydroxytoluene and butylated hydroxyanisole, a combination of two or more of them. Other scavengers that can be used include phenothiazine and anaerobic inhibitors, such as NPAL type inhibitors (tri-(N-nitroso-N-phenylhydroxylamine) aluminum salts) from Albemarle Corporation (Baton Rouge, La.). Alternatively, the radical scavenger can be selected from phenolic compounds, phenothiazine and anaerobic inhibitors.
[0098] Free radical scavengers are known, for example, in U.S. Pat. No. 9,475,968 and are commercially available. The amount of scavenger in the silicone hybrid pressure-sensitive adhesive composition will depend on various factors, including the type and amount of (meth)acryloyloxyalkyl groups in the starting materials (A) and (B), however, the scavenger may be present in an amount of 5 ppm to 2,000 ppm based on the combined weight of the starting materials (A), (B) and (C); alternatively 10 ppm to 1,500 ppm based on the same basis.
[0099] (H) Solvent
[0100] The starting material (H) in the organosilicon hybrid pressure-sensitive adhesive composition is a solvent. A solvent may be added during the preparation of the organosilicon hybrid pressure-sensitive adhesive composition, for example, to help mix and deliver one or more starting materials when preparing the organosilicon hybrid pressure-sensitive adhesive composition and / or to promote the coating of the organosilicon hybrid pressure-sensitive adhesive composition on a substrate, as described below. When preparing the organosilicon hybrid pressure-sensitive adhesive composition, some starting materials such as polyorganosilicate resins and / or hydrosilylation catalysts may be delivered in a solvent. Suitable solvents include organic liquids, examples of which include but are not limited to aromatic hydrocarbons, aliphatic hydrocarbons, ketones, esters, ethers, glycols, glycol ethers. Hydrocarbons include benzene, toluene, xylene, naphtha, hexane, cyclohexane, methylcyclohexane, heptane, octane, decane, hexadecane, isoparaffins (such as Isopar L (C11-C13), Isopar H (C11-C12)), hydrogenated polydecene. Suitable ketones include, but are not limited to, acetone, methyl ethyl ketone, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, methyl isobutyl ketone, diisobutyl ketone, acetonyl acetone, and cyclohexanone. Esters include ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, and isobutyl acetate. Ethers include diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, 1,2-dimethoxyethane, and 1,4-dioxane. Solvents having both ester and ether moieties include 2-methoxyethyl acetate, 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, and 2-butoxyethyl acetate; ethers and esters also include isodecyl neopentanoate, neopentyl glycol heptanoate, glycol distearate, dioctyl carbonate, diethylhexyl carbonate, propylene glycol n-propyl ether, propylene glycol n-butyl ether, ethyl-3 ethoxypropionate, propylene glycol methyl ether acetate, tridecyl neopentanoate, propylene glycol methyl ether acetate (PGMEA), propylene glycol methyl ether (PGME), dipropylene glycol methyl ether, or ethylene glycol n-butyl ether, octyl dodecyl neopentanoate, diisobutyl adipate, diisopropyl adipate, propylene glycol dioctanoate / dicaprate, octyl ether, and octyl palmitate. Alternatively, the solvent may be selected from polyalkylsiloxanes, ketones, glycol ethers, tetrahydrofuran, mineral oil, naphtha, or a combination thereof. Polyalkylsiloxanes having a suitable vapor pressure can be used as the solvent, and these polyalkylsiloxanes include hexamethyldisiloxane, octamethyltrisiloxane, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tris(trimethylsiloxy)methylsilane, tetrakis(trimethylsiloxy)silane, dodecamethylcyclohexasiloxane, octamethyltrisiloxane, decamethyltetrasiloxane, dodecamethylpentasiloxane, tetradecamethylhexasiloxane, hexadecamethylheptasiloxane, heptamethyl-3-{(trimethylsilyl)oxy}trisiloxane, hexamethyl-3,3-bis{(trimethylsilyl)oxy}trisiloxane, pentamethyl{(trimethylsilyl)oxy}cyclotrisiloxane, and combinations thereof.Low molecular weight polyalkylsiloxanes such as 0.5 cSt to 1.5 cSt polydimethylsiloxane are known in the art and are available under the trade name DOWSIL. TM 200 Fluid and DOWSIL TM OS fluids are commercially available and are commercially available from Dow Silicones Corporation. Alternatively, the solvent may be selected from: aliphatic hydrocarbons, aromatic hydrocarbons, ethers, esters, and solvents having both ether and ester moieties.
[0101] The amount of solvent will depend on a variety of factors, including the type of solvent selected, and the amount and type of other starting materials selected. However, when present, the amount of solvent can be 0 wt % to 90 wt % based on the combined weight of all starting materials in the silicone hybrid pressure-sensitive adhesive composition, alternatively 0 wt % to 60 wt % based on the same basis.
[0102] (I) Additives
[0103] The silicone hybrid pressure-sensitive adhesive composition may also optionally include additives such as ii) synergists, iii) chain transfer agents (hydrogen donors), iii) sensitizers, combinations of two or more of additives ii) to iv). The above additives may help improve UV sensitivity and reduce one or more of oxygen inhibition and adhesion of the silicone hybrid pressure-sensitive adhesive when exposed to UV radiation. Suitable types of additives are summarized in "The formulator's guide to anti-oxygen inhibition additives", Progress in Organic Coatings, Vol. 77, No. 11 (2014): pp. 1789-1798, Husár, Branislav et al. and PCT Publication WO2017182638A1. The type of additive is not particularly limited, however, some additives, especially additives containing a mercapto group, a phosphine or a phosphine oxide group, may inhibit the hydrosilylation reaction catalyst, and therefore, when such additives are included, it is necessary to control the appropriate amounts of (D) the hydrosilylation reaction catalyst and (I) the additive and / or adjust the curing temperature / time. The amount of the additive may be 0 to 5 parts by weight, alternatively 0 to 2 parts by weight per 100 parts by weight of the starting material (A). Examples of commercially available additives are as follows.
[0104] The synergist may be selected from the following amine-containing compounds: tertiary amines, glycine, oximes, aminobenzoates, acrylated amines, amine-modified acrylates, and combinations of at least two of these synergists. Examples of tertiary amines and aminobenzoates are commercially available and include, but are not limited to, N-methyldiethanolamine (CAS#105-59-9; Sigma-Aldrich), p-tolyldiethanolamine (CAS#3077-12-1), N-ethyldiisopropylamine (CAS#7087-68-5, Sigma-Aldrich), 2-(diisopropylamino)ethanol (CAS#96-80-0, Sigma-Aldrich), N-phenylglycine (CAS#103-01-5, TCI), Speedcure PDO (Lambson), ethyl 4-(dimethylamino)benzoate (CAS#10287-53-3, TCI), 2-ethylhexyl 4-(dimethylamino)benzoate (CAS#21245-2-3), Speedcure EDB (Lamson), Speedcure DMB (Lamson), Speedcure EHA (Lamson), Speedcure BDMB (Lamson), Speedcure XFLM01 (Lamson), Speedcure XFLM02 (Lamson), Speedcure EMD (Lamson), Speedcure BEDB (Lamson), Speedcure 7040 (Lamson), Speedcure EPD (Lamson), dimethylamine borane (CAS#74-94-2, Sigma-Aldrich), N-vinyl pyrrolidone (BASF).Examples of amine-modified acrylates and acrylated amines are also commercially available and include, but are not limited to, 2-(dimethylamino)ethyl methacrylate (CAS#2867-47-2, TCI), 2-(dimethylamino)ethyl acrylate (CAS#2439-35-2, TCI), N-[3-(dimethylamino)propyl]acrylamide (CAS#3845-76-9, TCI), Ebecryl P115 (Allnex), Ebecryl 7100 (Allnex), Ebecryl 80 (Allnex), Ebecryl 81 (Allnex), Ebecryl 83 (Allnex), Ebecryl 85 (Allnex), Ebecryl 880 (Allnex), Ebecryl LEO10551 (Allnex), Ebecryl LEO10552 (Allnex), Ebecryl LEO10553 (Allnex), Ebecryl 3600 (Allnex), Ebecryl 3703 (Allnex), DEAEMA (BASF), DMAEMA (BASF), TBAEMA (BASF), Genomer 5271 (Rahn), Genomer 5142 (Rahn), Genomer 5161 (Rahn), Genomer 5275 (Rahn), CN UVA 421 (Sartomer), CN3702 (Sartomer), CN3715 (Sartomer), CN3715 LM (Sartomer), CN3755 (Sartomer), CN381 (Sartomer), CN 386 (Sartomer), CN501 (Sartomer). The amount of the synergist may be 0.01 to 10 parts by weight, alternatively 0.1 to 2.0 parts by weight per 1 part by weight of the photoinitiator (E).
[0105] The chain transfer agent may be selected from mercapto-containing compounds and any other hydrogen donors. Examples are pentaerythritol tetrakis (3-mercaptopropionate) (CAS#7575-23-7; Sigma-Aldrich), trimethylolpropane tris (3-mercaptopropionate) (CAS#33007-83-9; Sigma-Aldrich), tris (trimethylsilyl) silane (CAS#1873-77-4, Alfa Aesar), 3-mercaptopropyl (dimethoxy) methyl silane (CAS#31001-77-1; TCI), (3-mercaptopropyl) trimethoxy silane (CAS#4420-74-0; TCI), mercaptosiloxane (CAS 102783-03-9; Gelest) and 1-hexanethiol (CAS#111-31-9, Sigma-Aldrich). The amount of the chain transfer agent may be 0.01 to 10 parts by weight, alternatively 0.1 to 2.0 parts by weight, per 1 part by weight of the photoinitiator (E).
[0106] Alternatively, the synergist may be a sensitizer, such as those disclosed in PCT Publication WO2015194654A1 and U.S. Patent No. 4,250,053. Available sensitizers include 2-isopropylthioxanthone, 1,3-diphenyl-2-pyrazoline, and 1,3-diphenylisobenzofuran. Other examples of sensitizers include anthracene compounds, 4-methoxy-1-naphthol, fluorene, pyrene, and diphenylethylene. Examples of anthracene compounds include anthracene, 9,10-dimethoxyanthracene, 9,10-diethoxyanthracene, 9,10-dipropoxyanthracene, 2-ethyl-9,10-dimethoxyanthracene, 2-ethyl-9,10-diethoxyanthracene, 2-ethyl-9,10-dipropoxyanthracene, 4'-nitrobenzyl-9,10-dimethoxyanthracene-2-sulfonate, 4'-nitrobenzyl-9,10-diethoxyanthracene-2-sulfonate, and 4'-nitrobenzyl-9,10-dipropoxyanthracene-2-sulfonate. Sensitizers are commercially available, for example, under the trade names Anthracure UVS-1331, 1221, 1101, and ET-2111 (manufactured by Kawasaki Kasei Kogyo Co., Ltd.). The amount of the sensitizer may be 0.01 to 10 parts by weight, alternatively 0.1 to 2.0 parts by weight, per 1 part by weight of the photoinitiator (E).
[0107] (J) Filling
[0108] The organosilicon hybrid pressure-sensitive adhesive composition may optionally further comprise an inorganic filler, for example a silica filler, such as fumed silica and / or precipitated silica. Without wishing to be bound by theory, it is believed that because the adhesive article prepared using the organosilicon hybrid pressure-sensitive adhesive composition may be susceptible to a certain external pressure due to an extremely low crosslinking density, the addition of fillers may enhance the cohesive strength (or mechanical strength or toughness). However, the amount and type of filler should be selected so that the filler does not significantly affect the ability of the organosilicon hybrid pressure-sensitive adhesive composition to adhere to and conform to uneven surfaces. Examples of surface-treated fumed silica for use include commercially available treated silica, such as those sold under the trade name AEROSIL TM Such as AEROSIL TM R8200, R9200, R812, R812S, R972, R974, R805, R202 were purchased from Degussa Corporation; TM ND-TS, TS610 or TS710 are available from Cabot Corporation; TM Such as DM-10, DM-20S, DM-30, HM-30S, MT-10, PM-20L, QS-10, QS-20A and QS-25C are available from Tokuyama Corporation. The amount of the starting material (J) depends on various factors, including the selected additives and the conditions used to prepare the silicone hybrid pressure-sensitive adhesive composition, however, based on the combined weight of the starting materials (A) and (B), the amount of filler may be 0 wt % to 30 wt %, alternatively 1 wt % to 30 wt %, alternatively 1 wt % to 20 wt %, and alternatively 5 wt % to 15 wt %.
[0109] (K) Bis-SiH-terminated polydiorganosiloxane
[0110] Optionally, in addition to the starting material (C) in the silicone hybrid pressure-sensitive adhesive composition, a bis-SiH-terminated polydiorganosiloxane may be used. The polydiorganosiloxane may have a unit formula M H 2D k , where M H and D units are as described above, and the subscript k ≥ 1, alternatively 1 ≤ k ≤ 500. Suitable polydiorganosiloxanes for the starting material (K) include dimethylhydrogensiloxy-terminated polydimethylsiloxane and dimethylhydrogensiloxy-terminated polydiphenylsiloxane. When present, the weight ratio of the starting material (K) to the starting material (C) [(K) / (C) ratio] may be 0.25 / 1 to 4 / 1.
[0111] When selecting starting materials for the above-described silicone hybrid pressure-sensitive adhesive composition, there may be overlap between the types of starting materials because some of the starting materials described herein may have more than one function. For example, some reducing agents may also function as hydrosilylation reaction inhibitors (e.g., phosphines such as triphenylphosphine). When additional starting materials are added to the silicone hybrid pressure-sensitive adhesive composition, the additional starting materials are different from each other and from the desired starting materials in the silicone hybrid pressure-sensitive adhesive composition.
[0112] Method for preparing silicone hybrid pressure-sensitive adhesive composition
[0113] The silicone hybrid pressure-sensitive adhesive composition can be prepared by a method comprising the steps of combining all starting materials by any convenient means, such as mixing at RT or at elevated temperature. For example, when the silicone hybrid pressure-sensitive adhesive composition is prepared at elevated temperature and / or the silicone hybrid pressure-sensitive adhesive composition is prepared as a one-part composition, a hydrosilylation reaction inhibitor can be added before the hydrosilylation reaction catalyst.
[0114] Alternatively, the organosilicon hybrid pressure-sensitive adhesive composition can be prepared as a multi-part composition, for example, when the organosilicon hybrid pressure-sensitive adhesive composition will be stored for a long period of time before use. In the multi-part composition, the hydrosilylation reaction catalyst is stored in a separate part from any starting material having silicon-bonded hydrogen atoms (e.g., polyorganohydrogensiloxane), and the parts are combined just before the organosilicon hybrid pressure-sensitive adhesive composition is used. For example, a two-part composition can be prepared by combining starting materials in any convenient manner (such as mixing) to form a base part, and these starting materials include starting material (C) polyorganohydrogensiloxane, all or part of starting materials (A) and (B) and optionally all or part of (H) solvent and optionally one or more other additional starting materials mentioned above. The curing agent can be prepared by combining starting materials in any convenient manner (such as mixing), and these starting materials include: starting material (D) hydrosilylation reaction catalyst and all or part of starting materials (A) and (H) and optionally one or more other additional starting materials mentioned above. The starting materials can be mixed at ambient temperature or at elevated temperature. The starting material (F) hydrosilylation reaction inhibitor may be included in one or more of the base part, the curing agent part or a separate additional part. The starting material (B) polyorganosilicate resin may be added to the base part, the curing agent part or a separate additional part. The starting material (E), the photoradical initiator and the starting material (G), the radical scavenger may be added to the base part or a separate additional (third) part. When a two-part composition is used, the weight ratio of the amount of the base part to the amount of the curing agent part may be in the range of 1:1 to 10:1. The silicone hybrid pressure-sensitive adhesive composition will be cured via a hydrosilylation reaction to form a pressure-sensitive adhesive.
[0115] Preparation of adhesive products
[0116] The above method may also include one or more additional steps. The organosilicon hybrid pressure-sensitive adhesive composition prepared as described above can be used to form an adhesive article on the surface of a substrate, for example, an organosilicon hybrid pressure-sensitive adhesive (prepared by thermally curing the above organosilicon hybrid pressure-sensitive adhesive composition). Therefore, the above method may also include applying the organosilicon hybrid pressure-sensitive adhesive composition to a substrate, such as a web-based substrate.
[0117] The silicone hybrid pressure-sensitive adhesive composition can be applied to the web-based substrate by any convenient means. For example, the silicone hybrid pressure-sensitive adhesive composition can be applied to the web-based substrate by a gravure coater, a photographic coater, a photo-gravure coater, a roll coater, a reverse roll coater, an air knife coater, or a curtain (slot die) coater.
[0118] The substrate can be any material that can withstand the curing conditions (described below) for curing the pressure-sensitive adhesive curable composition to form a silicone hybrid pressure-sensitive adhesive on the substrate. For example, any substrate that can withstand heat treatment at a temperature equal to or greater than 120°C, alternatively 150°C is suitable. Examples of materials suitable for such substrates include plastic films, such as polyimide (PI), polyetheretherketone (PEEK), polyethylene naphthalate (PEN), liquid crystal polyarylate, polyamideimide (PAI), polyether sulfide (PES), polyethylene terephthalate (PET), PE (polyethylene) and PP (polypropylene). The thickness of the substrate is not critical, however, the thickness can be in the range of 25 microns to 300 microns. The substrate is preferably transparent, alternatively, an opaque substrate can be used, provided that the opaque substrate allows the silicone hybrid pressure-sensitive adhesive to be exposed to UV radiation.
[0119] In order to improve the bonding of the silicone hybrid pressure-sensitive adhesive to the substrate, the method may also optionally include treating the surface of the substrate before applying the silicone hybrid pressure-sensitive adhesive composition. Treating the substrate may be performed in any convenient manner, such as applying a primer, or subjecting the substrate to corona discharge treatment, etching or plasma treatment before applying the silicone hybrid pressure-sensitive adhesive composition to the substrate.
[0120] Adhesive articles (such as protective films) can be prepared by applying the above-mentioned silicone hybrid pressure-sensitive adhesive composition to the surface of the above-mentioned substrate. The method may also optionally include removing all or part of the solvent (when present) before and / or during curing. Removal of the solvent can be carried out by any convenient means, such as heating at a temperature that evaporates the solvent without completely curing the silicone hybrid pressure-sensitive adhesive composition via a hydrosilylation reaction, for example, heating at a temperature of 70°C to 120°C, alternatively 50°C to 100°C, and alternatively 70°C to 80°C for a time sufficient to remove all or part of the solvent (e.g., 30 seconds to 1 hour, alternatively 1 minute to 5 minutes). Therefore, the method also includes curing the silicone hybrid pressure-sensitive adhesive composition (which can remove part or all of the solvent during the drying step) via a hydrosilylation reaction at room temperature or by heating at a temperature of 60°C to 220°C, alternatively 70°C to 170°C, and alternatively 80°C to 160°C for a time sufficient to form a silicone hybrid pressure-sensitive adhesive on the surface of the substrate (e.g., 30 seconds to one hour, alternatively 15 minutes to 45 minutes). Drying and / or hydrosilylation curing can be performed by placing the substrate in an oven. The amount of the silicone hybrid pressure-sensitive adhesive composition to be applied to the substrate depends on the specific application, however, the amount can be sufficient to allow the silicone hybrid pressure-sensitive adhesive to have a thickness of 50 microns to 1,000 microns, alternatively 100 microns to 700 microns, and alternatively 200 microns to 600 microns after curing;.
[0121] Thus, a method for forming an adhesive article comprising a silicone hybrid pressure-sensitive adhesive layer on a surface of a substrate comprises:
[0122] Optionally 1) treating the surface of the substrate as described above;
[0123] 2) applying the above organosilicon hybrid pressure-sensitive adhesive composition to the surface of a substrate, and
[0124] Optionally 3) removing all or a portion of the solvent, if present;
[0125] 4) The silicone hybrid pressure-sensitive adhesive composition is heated to form a silicone hybrid pressure-sensitive adhesive layer on the surface of the substrate.
[0126] If necessary, the above method steps 2) to 4) can be repeated one or more times to increase the thickness of the silicone hybrid pressure-sensitive adhesive. (The desired thickness is described below in the "Usage Method"). The above method can also optionally include applying a removable release liner to the silicone hybrid pressure-sensitive adhesive layer opposite to the substrate, for example, to protect the silicone hybrid pressure-sensitive adhesive before use. The release liner can be removed before using the adhesive article. The obtained organic silicon hybrid pressure-sensitive layer of the above cured film contains free (meth) acryloyl groups, which can be analyzed by Fourier transform infrared (FT-IR) spectroscopy, and their relative amount in the cured film and their reaction when exposed to UV radiation can be monitored by the vibration absorption intensity of unsaturated bonds in the FT-IR spectrum, as shown in the following literature: "UV coatings: basics, recent developments and new applications", page 33 (Elsevier; December 21, 2006), Schwalm; Polymer Chemistry., 2013; Vol. 4, No. 8: pp. 2449-2456, Espeel. At about 1296 cm -1 and 938cm 1 Free (meth)acryloyl groups were detected in the silicone hybrid pressure-sensitive adhesive prepared by using the starting material (A).
[0127] How to use
[0128] The above-described adhesive article may be used in a method comprising the steps of:
[0129] 5) applying the adhesive article (prepared as described above) to the uneven surface such that the surface of the silicone hybrid pressure-sensitive adhesive layer opposite the substrate contacts the uneven surface;
[0130] Optionally 6) applying heat and / or pressure to the adhesive article and the uneven surface; and
[0131] 7) exposing the silicone hybrid pressure-sensitive adhesive layer to UV radiation,
[0132] The silicone hybrid pressure sensitive adhesive layer is thereby made to conform to the non-uniform surface.The non-uniform surface may be any part of an (opto)electronic device having features thereon, such as all or part of a ball grid array or a matrix grid array.
[0133] The uneven surface may have a linear, inverted round (circular) or rectangular pattern, and its pattern may be concave or convex. The width of the line, the diameter of the circle and the length of one side of the rectangle may be 0.1 mm to 10 mm. The height of the uneven thickness applied to the member is not particularly limited, but may be in the range of 1 μm to 600 μm or less. In addition, from the perspective of the influence of film formation and uneven thickness recovery, the ratio of the thickness of the silicone hybrid pressure-sensitive adhesive layer to the height of the uneven thickness (the thickness of the silicone hybrid pressure-sensitive adhesive layer / the height of the uneven thickness) may be 1.1 to 5, alternatively 1.5 to 4. Specific examples of lamination on uneven surfaces in the industrial field are described in U.S. Patent 8,920,592, U.S. Patent Application No. 13 / 722,276 (optical device); U.S. Patent 6,906,425 to Stewart, U.S. Patent 6,000,603, Patent Application WO2015182816 (electronic device), U.S. Patent Application 16 / 244,860 (US20190148598, micro-assembled optical device). Silicone hybrid pressure-sensitive adhesive compositions and methods and uses thereof can be used to replace the adhesives in these references.
[0134] The temperature at which the adhesive article tends to fully conform to the 3-D features of the uneven surface can be RT to 200° C. When pressure is applied to the adhesive article to conform it to the uneven surface, the applied pressure can typically be 0.05 MPa or more, alternatively 0.1 MPa or more, and 2 MPa or less, alternatively 1 MPa or less. In order to completely remove voids (to obtain a laminate free of bubbles), a vacuum of typically 25 Torr or less, alternatively 5 Torr or less, can be applied to the complex structure of the 3-D features of the uneven surface during lamination.
[0135] The ultraviolet irradiation in step 7) can be performed using a general ultraviolet irradiation device, for example, a surface type or conveyor type ultraviolet irradiation device, wherein a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultrahigh-pressure mercury lamp, a xenon lamp, a metal halide lamp, an electrodeless lamp, an ultraviolet light emitting diode, etc. are used as a light source. The ultraviolet irradiation dose is generally 0.1 W / cm 2 Up to 5W / cm 2Lasts from 5 to 120 seconds (=0.5 J / cm 2 Up to 600J / cm 2 ).
[0136] Example
[0137] These examples are intended to illustrate some embodiments of the invention and should not be construed as limiting the scope of the invention described in the claims.The starting materials used in these examples are described in Table 1.
[0138] Table 1 - Starting materials used in the examples
[0139]
[0140]
[0141]
[0142] Brand: DOWSIL TM The starting materials are commercially available from Dow Silicones Corporation and / or its subsidiaries.
[0143] In this Reference Example 1, a bisvinyl-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer shown as starting material A-1 in Table 1 above was synthesized as follows. 3-methacryloxypropylmethyldimethoxysilane (120.00 g, DOWSIL TMZ-6033) and 0.1N HCl (128.87g), and use a magnetic stirring bar to mix at about 23°C. Use a simple distillation glassware device to evacuate to about 20mmHg for 1.5 hours. After 1.5 hours, release the vacuum and add dihydroxy-terminated polydimethylsiloxane (786.50g, OH fluid) together with 0.23g (G-1) MEHQ to the reaction solution. Take out the magnetic stirring bar, and use a Teflon paddle with a glass stirring rod to mix the solution. Evacuate to about 5mmHg, and heat the reaction system to 80°C for 1.5 hours. Remove the simple distillation glassware device, and use the Dean Stark distillation device for the final reaction step. Add (H-1) toluene (380g, Sigma-Aldrich) and dimethylvinylsiloxy-terminated polydimethylsiloxane (2.87g, end-capping agent) to the reaction solution. The solution is then heated to 111°C-115°C, and 0.3 mL of phosphazene catalyst is added at 90°C. The overhead distillate is collected in a Dean Stark trap, and an additional 0.3 mL of phosphazene catalyst is added. The solution is maintained at toluene reflux for 1 hour. The heat source is removed, and the solution is cooled. At about 60°C, trihexylamine (0.3 g, Sigma Aldrich) is added to the reaction solution and mixed for 2 hours. And, the solution is heated to 120°C with nitrogen / 2% oxygen bubbling, continues for 1 hour, and cooled to RT. The solid content of the solution is adjusted to 75% by adding additional toluene. Then, a product dissolved in toluene is obtained. Based on 13 C-NMR and 29 Si-NMR analysis shows that the obtained bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer contains the following average unit formula: 4 3SiO 1 / 2 ) 0.00071 (R 4 2SiO 2 / 2 ) 0.99929 ; where each R 4 R is independently selected from methyl, methacryloyloxypropyl and vinyl; and the subscript represents the molar fraction. The methacryloyl content is the total R 4 The vinyl content is 2.406 mol% for the total R 4 0.012 mol%, and the methyl content is the total R 4The obtained bisvinyldimethylsiloxy terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer can also be represented by the unit formula: (ViMe2SiO)2(MaMeSiO) 136 (Me2SiO) 2679 .
[0144] In this Reference Example 2, a bisvinyl-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer shown as starting material A-2 in Table 1 above was synthesized as follows. 3-methacryloxypropylmethyldimethoxysilane (50.78 g, DOWSIL TM Z-6033) and 0.1N HCl (45.45g), and use a magnetic stirring bar to mix at about 23°C. Use a simple distillation glassware device to evacuate to about 20mmHg for 1.5 hours. After 1.5 hours, release the vacuum and add dihydroxy-terminated polydimethylsiloxane (550.00g, OH fluid) together with 0.16g (G-1) MEHQ to the reaction solution. Take out the magnetic stirring bar, and use a Teflon paddle with a glass stirring rod to mix the solution. Evacuate to about 5mmHg, and heat the reaction system to 80°C for 1.5 hours. Remove the simple distillation glassware device, and use the Dean Stark distillation device for the final reaction step. Add (H-1) toluene (300g, Sigma-Aldrich) and dimethylvinylsiloxy-terminated polydimethylsiloxane (2g, end-capping agent) to the reaction solution. The solution was then heated to 111°C-115°C, and 0.4 mL of phosphazene catalyst was added at 90°C. The overhead distillate was collected in a Dean Stark trap, and an additional 0.4 mL of phosphazene catalyst was added. The solution was maintained at toluene reflux for 1 hour. The heat source was removed, and the solution was cooled. At about 60°C, DVTMDZ (1 g, Sigma Aldrich) was added to the reaction solution and mixed for 2 hours. Also, the solution was heated to 120°C with nitrogen / 2% oxygen bubbling for 1 hour, and cooled to RT with gas bubbling. The solid content of the solution (which is the weight measured before and after drying at 150°C for 1 hour) was adjusted to 75% by adding additional toluene. Then, a product dissolved in toluene was obtained. Based on 13 C-NMR and 29Si-NMR analysis shows that the obtained bis(dimethylvinylsiloxy)-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer contains the following average unit formula: 4 3SiO 1 / 2 ) 0.00091 (R 4 2SiO 2 / 2 ) 0.99909 ; where each R 4 R is independently selected from methyl, methacryloyloxypropyl and vinyl; and the subscript represents the molar fraction. The methacryloyl content is the total R 4 1.325 mol% vinyl content for total R 4 0.015 mol%, and the methyl content is the total R 4 The obtained bis(dimethylvinylsiloxy)-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer may have an average unit formula of (ViMe2SiO)2(MaMeSiO) 58 (Me2SiO) 2130 Shown.
[0145] In this Reference Example 3, a bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer shown as starting material A-3 in Table 1 above was synthesized as follows. 3-methacryloxypropylmethyldimethoxysilane (33.3 g, DOWSIL TMZ-6033) and 0.1N HCl (45.45g), and use a magnetic stirring bar to mix at room temperature (about 23°C). Use a simple distillation glassware device to evacuate to about 20mmHg for 1.5 hours. After 1.5 hours, release the vacuum and add silanol-terminated dimethylsiloxane (600.00g, OH fluid) together with 0.23g (G-1) MEHQ to the reaction solution. Take out the magnetic stirring bar, and use a Teflon paddle with a glass stirring rod to mix the solution. Evacuate to about 5mmHg, and heat the reaction system to 80°C for 1.5 hours. Remove the simple distillation glassware device, and use the Dean Stark distillation device for the final reaction step. Add (H-1) toluene (300g, Sigma-Aldrich) and bis(dimethylvinylsiloxy)-terminated polydimethylsiloxane (2.2g, end-capping agent) to the reaction solution. The solution was then heated to 111°C-115°C, and 0.4 mL of phosphazene catalyst was added at 90°C. The overhead distillate was collected in a Dean Stark trap, and an additional 0.4 mL of phosphazene catalyst was added. The solution was maintained at toluene reflux for 1 hour. The heat source was removed, and the solution was cooled. At about 60°C, DVTMDZ (1 g, Sigma Aldrich) was added to the reaction solution and mixed for 2 hours. Also, the solution was heated to 120°C with nitrogen / 2% oxygen bubbling for 1 hour, and cooled to RT with gas bubbling. The solids content of the solution was adjusted to 75% by adding additional toluene. Then, a product dissolved in toluene was obtained. Based on 13 C-NMR and 29 Si-NMR analysis shows that the obtained bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer contains the following average unit formula: 4 3SiO 1 / 2 ) 0.00035 (R 4 2SiO 2 / 2 ) 0.99965 ; where each R 4 R is independently selected from methyl, methacryloyloxypropyl and vinyl; and the subscript represents the molar fraction. The methacryloyl content is the total R 4 The vinyl content of the total R 4 0.006 mol%, and the methyl content is the total R 4The obtained bisvinyldimethylsiloxy terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer can be represented as: (ViMe2SiO)2(MaMeSiO) 100 (Me2SiO) 5610 .
[0146] In this Reference Example 4, a bisvinyl-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer shown as starting material A-4 in Table 1 above was synthesized as follows. 3-methacryloxypropylmethyldimethoxysilane (13.7 g, DOWSIL TM Z-6033) and 0.1N HCl (24.37g), and use a magnetic stirring bar to mix at about 23°C. Use a simple distillation glassware device to evacuate to about 20mmHg for 1.5 hours. After 1.5 hours, release the vacuum and add dihydroxy-terminated polydimethylsiloxane (1179.49g, OH fluid) together with 0.34g (G-1) MEHQ to the reaction solution. Take out the magnetic stirring bar, and use a Teflon paddle with a glass stirring rod to mix the solution. Evacuate to about 5mmHg, and heat the reaction system to 80°C for 1.5 hours. Remove the simple distillation glassware device, and use the Dean Stark distillation device for the final reaction step. Add (H-1) toluene (550g, Sigma-Aldrich) and dimethylvinylsiloxy-terminated polydimethylsiloxane (2.2g, end-capping agent) to the reaction solution. The solution was then heated to 111°C-115°C, and 0.1 mL of phosphazene catalyst was added at 90°C. The overhead distillate was collected in a Dean Stark trap, and an additional 0.1 mL of phosphazene catalyst was added. The solution was maintained at toluene reflux for 1 hour. The heat source was removed, and the solution was cooled. At about 60°C, DVTMDZ (0.3 g, Sigma Aldrich) was added to the reaction solution and mixed for 2 hours. Also, the solution was heated to 120°C with nitrogen / 2% oxygen bubbling for 1 hour, and cooled to RT. The solids content of the solution was adjusted to 75% by adding additional toluene. Then, a product dissolved in toluene was obtained. Based on 13 C-NMR and 29 Si-NMR analysis shows that the obtained bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer contains the following average unit formula:4 3SiO 1 / 2 ) 0.00074 (R 4 2SiO 2 / 2 ) 0.99926 ; where each R 4 R is independently selected from methyl, methacryloyloxypropyl and vinyl; and the subscript represents the molar fraction. The methacryloyl content is the total R 4 The vinyl content of the total R 4 0.012 mol%, and the methyl content is the total R 4 The obtained bisvinyldimethylsiloxy terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer can be represented as: (ViMe2SiO)2ViMe2SiO(MaMeSiO) 10 (Me2SiO) 2679 .
[0147] In this Reference Example 5, a bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer shown as starting material A-5 in Table 1 above was synthesized as follows. 3-methacryloxypropylmethyldimethoxysilane (4.5 g, DOWSIL TMZ-6033) and 0.1N HCl (4.55g), and mixed at room temperature (about 23°C) using a magnetic stirring bar. Use a simple distillation glassware device to evacuate to about 20mmHg for 1.5 hours. After 1.5 hours, release the vacuum and add silanol-terminated dimethylsiloxane (786.5g, OH fluid) together with 0.23g (G-1) MEHQ to the reaction solution. Take out the magnetic stirring bar, and use a Teflon paddle with a glass stirring rod to mix the solution. Evacuate to about 5mmHg, and heat the reaction system to 80°C for 1.5 hours. Remove the simple distillation glassware device, and use the Dean Stark distillation device for the final reaction step. Add (H-1) toluene (450g, Sigma-Aldrich) and bis(dimethylvinylsiloxy)-terminated polydimethylsiloxane (5g, end-capping agent) to the reaction solution. The solution was then heated to 111°C-115°C and 0.1 mL of phosphazene catalyst was added at 90°C. The overhead distillate was collected in a Dean Stark trap and an additional 0.1 mL of phosphazene catalyst was added. The solution was kept at toluene reflux for 1 hour. About 80 g of overhead distillate was collected. The heat source was removed and the solution was cooled. At about 60°C, DVTMDZ (0.3 g, Sigma Aldrich) was added to the reaction solution and mixed for 2 hours. The solid content of the solution was adjusted to 75% by adding additional toluene. Then, a product dissolved in toluene was obtained. Based on 13 C-NMR and 29 Si-NMR analysis shows that the obtained bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer contains the following average unit formula: 4 3SiO 1 / 2 ) 0.00074 (R 4 2SiO 2 / 2 ) 0.99926 , where each R 4 R is independently selected from methyl, methacryloyloxypropyl and vinyl, and the subscript indicates the molar fraction. The methacryloyl content is the total R 4 0.097 mol% vinyl content for total R 4 0.022 mol%, and the methyl content is the total R 4The obtained bisvinyldimethylsiloxy terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer can also be represented by the unit formula: (ViMe2SiO)2(MaMeSiO)3(Me2SiO) 1536 .
[0148] In this Reference Example 6, a bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer shown as starting material A-6 in Table 1 above was synthesized as follows. 900 g of silanol-terminated dimethylsiloxane (786.5 g, OH fluid), 63 g of 3-methacryloxypropylmethyldimethoxysilane (DOWIL TM Z-6033), 6.3g of hexamethyldisiloxane and 180g of heptane were loaded into a 4-neck 2L flask equipped with a thermocouple, a mechanical stirrer, a water-cooled condenser and an air bubbler. Under vigorous stirring, 0.53mL of trifluoromethanesulfonic acid (Sigma-Aldrich) was added to the flask. Heat was applied and the tank temperature was raised to 73°C. Water, methanol and heptane began to be distilled off and collected in the Dean Stark. After about 1 hour, the reflux temperature gradually increased to 90°C. 3g of water was added to the flask and the azeotropic distillation process was continued. After 30 minutes, the tank temperature was raised to about 90°C, and another batch of 2.5g of water was added to the flask. After 1 hour and 40 minutes, the reflux temperature was raised to 96°C. In the above process, the water / methanol collected in the Dean Stark was discharged. The heat source was removed and 36g of Kyowaad TM 500SN (Kytowa Chemical Industry Co, Ltd) was added to the flask. The pot temperature was cooled to RT. After stirring for 3 hours, the solid was filtered out through a 0.45 μm filter membrane. The filtrate was rotary evaporated at 110°C and <1 torr for 1 hour. Then, the product was obtained. Based on 13 C-NMR and 29 Si-NMR analysis shows that the obtained bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer includes the following average unit formula: (R 4 3SiO 1 / 2 ) 0.00689 (R 4 2SiO 2 / 2 ) 0.99311 , where each R 4R is independently selected from methyl, methacryloyloxypropyl and vinyl, and the subscript indicates the molar fraction. The methacryloyl content is the total R 4 The vinyl content is 1.383 mol% of the total R 4 0.115 mol%, and the methyl content is the total R 4 The obtained bisvinyldimethylsiloxy terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer can also be represented by the unit formula: (ViMe2SiO)2(MaMeSiO)8(Me2SiO) 280 .
[0149] In this Reference Example 7, a bisvinyldimethylsiloxy-terminated poly(dimethyl / methyl, methacryloxypropyl)siloxane copolymer shown as starting material A-7 in Table 1 above was synthesized as follows. 3-methacryloxypropylmethyldimethoxysilane (30 g, DOWSIL TMZ-6033), silanol-terminated dimethyl, methylvinylsiloxane (9.5g, ME2 / MeVi diol) and 0.1N HCl (4.55g), and mixed at room temperature (about 23°C) using a magnetic stirring bar. Use a simple distillation glassware device to evacuate to about 20mmHg for 1.5 hours. After 1.5 hours, release the vacuum and add silanol-terminated dimethylsiloxane (300g, OH fluid) together with 0.03g (G-1) MEHQ to the reaction solution. Take out the magnetic stirring bar, and use a Teflon paddle with a glass stirring rod to mix the solution. Evacuate to about 5mmHg, and heat the reaction system to 80°C for 1.5 hours. Remove the simple distillation glassware device, and use the Dean Stark distillation device for the final reaction step. Add (H-1) toluene (200g, Sigma-Aldrich) to the reaction solution. The solution was then heated to 111°C-115°C and 0.1 mL of phosphazene catalyst was added at 90°C. The overhead distillate was collected in a Dean Stark trap and an additional 0.1 mL of phosphazene catalyst was added. The solution was kept at toluene reflux for 1 hour. About 80 g of overhead distillate was collected. The heat source was removed and the solution was cooled. At <50°C, HMDZ (1.31 g, Sigma Aldrich) was added to the reaction solution and mixed for 1 hour. Water was added and mixed for 30 minutes. The temperature was then raised to 110°C to remove water, volatile residues and ammonia for 1 hour. The solids content of the solution was adjusted to 40%. Then, a product dissolved in toluene was obtained. Based on 13 C-NMR and 29 Si-NMR analysis shows that the obtained bistrimethylsiloxy-terminated poly(dimethyl / methyl, vinyl / methyl, methacryloxypropyl)siloxane copolymer contains the following average unit formula: (R 4 3SiO 1 / 2 ) 0.00004 (R 4 2SiO 2 / 2 ) 0.99916 , where each R 4 R is independently selected from methyl, methacryloyloxypropyl and vinyl, and the subscript indicates the molar fraction. The methacryloyl content is the total R 4 1.55 mol% vinyl content for total R 4 0.4 mol%, and the methyl content is the total R 4The obtained bisvinyldimethylsiloxy terminated poly(dimethyl / methyl, vinyl / methyl, methacryloxypropyl)siloxane copolymer can also be represented by the unit formula: (Me3SiO)2(MaMeSiO) 155 (ViMeSiO) 40 (Me2SiO) 4795 .
[0150] In this Reference Example 8, a methacryloxy and vinyl functional polyorganosilicate resin shown as starting material B-1 in Table 4 was synthesized as follows. The following starting materials were charged into a 3-neck 2L flask of Dean Stark equipped with a thermocouple, a mechanical stirrer, a water-cooled condenser and a N2 bubbler: 742.2 g of a 75% xylene solution of (B-3) dimethylvinylated and trimethylated silica (Mn=4830, Mw=5030), 39.5 g of 3-methacryloxypropylmethyldimethoxysilane, 0.20 g of 4-methoxyphenol and 120 g of toluene. Under vigorous stirring, 1.2 g of trifluoromethanesulfonic acid (from Sigma-Aldrich) was slowly added and heated to 60°C. After 1 hour, 9.18 g of water was added and stirred for 2 hours. After 1 hour, the reflux temperature was gradually increased to 90°C to collect methanol. The reflux temperature was gradually increased to 127°C. In the above process, the water / methanol collected in the Dean Stark was discharged. After the anhydrous distillation, the flask contents were refluxed for another 2 hours while maintaining the temperature. Thereafter, the heat source was removed and 22.8 g of calcium carbonate (from Sigma-Aldrich) and 50 g of sodium sulfate (from Sigma-Aldrich) were added to the flask. The flask was cooled to RT. After stirring for 3 hours, the solids were filtered out through a 0.45 μm filter membrane. The resulting methacryloxy-functional polyorganosilicate resin was a liquid (solids content = 68.4%) in solvent (xylene and toluene). The methacryloxy-functional polyorganosilicate resin is represented by the following average formula: (Me3SiO 1 / 2 ) 0.40 (ViMe2SiO 1 / 2 ) 0.039 (MaMeSiO 2 / 2 ) 0.024 (SiO 4 / 2 ) 0.537 (OH) 0.01 , where methacryloyl content = total R 4 1.79 mol%; vinyl content = total R 42.86 mol%; methyl content = total R 4 95.36 mol% [methacryloyl content = 0.332 mmol / g, Vi content = 0.532 mmol / g, total reactive groups = 0.864 mmol / g].
[0151] In this Reference Example 9, a methacryloxy-functional polyorganosilicate resin shown as starting material B-4 in Table 4 was synthesized as follows. The following starting materials were charged into a 3-neck 2L flask of Dean Stark equipped with a thermocouple, a mechanical stirrer, a water-cooled condenser and a N2 bubbler: 450.37 g of a 75% xylene solution of (B-2) trimethylated silica (Mn=3065, Mw=5664), 55.76 g of 3-methacryloxypropylmethyldimethoxysilane, 0.13 g of (G-1) MEHQ and 120 g of toluene. Under vigorous stirring, 0.6 g of trifluoromethanesulfonic acid (Sigma-Aldrich) was slowly added and heated to 60°C. After 1 hour, 9 g of water was added at RT and stirred for 1 hour. Then, 60 g of methanol and 1.73 g of 11N KOH were subsequently added. After 1 hour, the temperature was gradually raised to 90°C to collect methanol. The reflux temperature was gradually increased to 115°C. In the above process, the water / methanol collected in the Dean Stark was discharged. After the anhydrous distillation, the flask contents were refluxed for another hour while maintaining the temperature. Thereafter, the heat source was removed and 0.94 g of acetic acid (Sigma-Aldrich) was added to the flask. The flask was cooled to RT. After stirring for 3 hours, the solids were filtered out through a 0.45 μm filter membrane. The resulting methacryloxy-functional polyorganosilicate resin was a liquid (solids content = 68.2%) in a solvent (xylene and toluene). The methacryloxy-functional polyorganosilicate resin is represented by the following average formula: (Me3SiO 1 / 2 ) 0.476 (MaMeSiO 2 / 2 ) 0.048 (SiO 4 / 2 ) 0.476 , where methacryloyl content = total R 4 3.13 mol%; methyl content = total R 4 96.88 mol% [methacryloyl content = 0.626 mmol / g, total reactive groups = 0.626 mmol / g].
[0152] In this reference example 10, a silicone hybrid pressure-sensitive adhesive composition and a comparative composition are prepared. The starting materials (A) and (B) are soluble in a solvent. The general procedure is as follows: To prepare a sample labeled Inv.1, a solution is prepared by mixing the following starting materials in a mixer: 133.33 g of 100 g of starting material (A-1) and about 300 ppm (G-1) dissolved in toluene (H-1); 140 g of a solution of 95.76 g of starting material (B-3) dissolved in a solvent; 10.8 g of polyorganohydrogensiloxane (C-2); 8.3 g of a photoradical initiator (E-1); 0.2 g of a hydrosilylation reaction inhibitor (F-1). After mixing the above starting materials, the obtained solution is further mixed with 0.3 g of a hydrosilylation reaction catalyst (D-1). The above starting materials are mixed with the above solution to produce a silicone hybrid pressure-sensitive adhesive composition. The obtained composition is used to manufacture an adhesive tape. The lamination characteristics and adhesion of the produced adhesive tape were evaluated. Comparative Examples and Inv.2-25 were prepared in the same manner using the starting materials and amounts in the table. In order to prepare a solvent-free sample labeled Inv.26, a solution was prepared by mixing the following starting materials in a mixer: 100 g of starting material (A-6) with about 300 ppm (G-1), and 458.21 g of a solution of 312.5 g of starting material (B-4) in xylene and toluene was vaporized under reduced pressure at 110°C. Then, 2.8 g of polyorganohydrogensiloxane (C-2) was added; 6.2 g of a photoradical initiator (E-1); and 0.1 g of a hydrosilylation reaction inhibitor (F-1). After mixing the above starting materials, the obtained fluid was further mixed with 0.1 g of a hydrosilylation reaction catalyst (D-1). Inventive Examples 27-29 were prepared in the same manner using the starting materials and amounts in the table. Tables 2-5 show the starting materials used (described in detail in Table 1) and their amounts [based on solids in grams and (solution in grams)]. The value (solution in grams) means that the starting materials were first dissolved in the solvent and represents the weight of the solution in grams. The value based on solids represents the amount of starting materials excluding the solvent.
[0153] In this Reference Example 11, a silicone hybrid pressure-sensitive adhesive tape was formed using the silicone hybrid pressure-sensitive adhesive composition prepared according to Reference Example 9. The composition (Comp. 1-12 and Inv. 1-25) containing a solvent was coated on a polyethylene terephthalate (PET) film (50 μm), and then dried by heating the coated film at 110° C. for 20 minutes and then at 150° C. for 4 minutes to have a thickness of 200 μm. On the dried surface, each composition was repeatedly coated, and then dried by heating the coated film at 110° C. for 20 minutes and then at 150° C. for 6 minutes. The silicone hybrid pressure-sensitive adhesive layer had a total thickness of 400 μm after curing. The solvent-free composition (Inv. 26-29) was coated on a polyethylene terephthalate (PET) film (50 μm), and then dried by heating the coated film at 110° C. for 20 minutes and then at 150° C. for 5 minutes to have a thickness of 400 μm. The obtained silicone hybrid pressure-sensitive adhesive sheet was attached to a polyethylene terephthalate film (release liner) with a fluorine-containing coating by a laminator, and the resulting product was aged at room temperature for 1 day.
[0154] In this Reference Example 11, the silicone hybrid pressure-sensitive adhesive tape prepared according to Reference Example 10 was used to evaluate the adhesion to the uneven surface. Then, the obtained silicone hybrid pressure-sensitive adhesive sheet was cut into 1 inch wide tape strips, which were placed on the uneven surface. The substrate size = 27 mm × 27 mm × 2.46 mm, with a 320-pin (ball) array on the surface; ball diameter = 0.75 mm, ball height = 0.35 mm, center pitch = 1.27 mm, supplied by Fujitsu Semiconductor Limited, the ball grid array (or BGA package) with the product name BGA-320P-M06 was used as the uneven surface. The tape strips were bonded to the BGA package using a laminator at RT for 30 minutes, or at 90°C for 30 minutes. A pressure of 0.5 MPa was applied to the laminate under vacuum at <1 torr (vacuum laminator purchased from Shindo Eng. Lab. Ltd.). After the laminate is extracted from the chamber, it is transferred to a UV curing machine and then irradiated with UV from the top of the base film. The light source is a 365nm LED (FireJet TM FJ100). Power = 0.6 mW, time = 30 seconds. Finally, visual inspection was performed by microscope to check whether the silicone hybrid pressure-sensitive adhesive tape was well laminated without delamination and / or without voids. The visual inspection results are shown in Tables 2-4 below. The value 'A' means that the sample is not delaminated and has no voids. The value 'B' means that the sample is partially delaminated and / or has voids. The value 'C' means that the sample is completely delaminated.
[0155] In this Reference Example 12, the silicone hybrid pressure-sensitive adhesive tape prepared according to Reference Example 10 was used to evaluate the adhesion to uneven surfaces. Each silicone hybrid pressure-sensitive adhesive tape was placed on a stainless steel (SUS) plate and bonded to it by moving a 2 kg weight rubber-lined pressure roller back and forth twice on the strip. The assembly was kept at RT for 1 hour. The tape was then irradiated with UV from the top of the base film. The light source was a 365 nm LED (FireJet TM FJ100). Power = 0.6mW, time = 30 seconds. Finally, measure the adhesion (g / inch) required for peeling the tape off the stainless steel plate by pulling at a speed of 300mm / min and an angle of 180 ° and record it in the following table 2-5. The adhesion of all records in Table 2-5 is the value when "adhesion failure" occurs. "Adhesion failure" indicates that the pressure-sensitive adhesive on the base film is removed from the steel plate without residual adhesive. "Cannot be measured" means that when removing (peeling off) from the film with fluorine-containing coating, the pressure-sensitive adhesive prepared in Reference Example 10 is torn or left on both the film (peeling liner) with fluorine-containing coating and the base film because of insufficient crosslinking. "Cohesive failure" indicates that after removing the tape, the pressure-sensitive adhesive is left on both the base film and the stainless steel plate (or adherend).
[0156] In this Reference Example 13, the silicone hybrid pressure-sensitive adhesive tape prepared according to Reference Example 10 was used to evaluate the change in adhesion to a uniform surface under the following three different conditions: before / after UV irradiation, and heat treatment after UV irradiation. Each silicone hybrid pressure-sensitive adhesive tape was placed on a stainless steel (SUS) plate and bonded to it by moving a 2 kg weight rubber-backed pressure roller back and forth twice on the strip. The assembly was kept at RT for 1 hour. Then, the adhesion (g / inch) required to peel the tape off the stainless steel plate at a speed of 300 mm / min and an angle of 180° was measured under the following three different conditions: 1) Adhesion before UV irradiation; 2) Adhesion after UV irradiation (the light source was 365 nm LED (FireJet TM FJ100); Power = 0.6 mW, Time = 30 seconds. ); 3) Adhesion after UV irradiation followed by exposure to a 125°C convection oven for 1 hour and cooling to RT. All adhesion reported in Table 7 are values when "adhesion failure" occurred.
[0157] Tables 2-5 show the starting materials (described in detail above) and their amounts (in grams), as well as the test results after lamination to a non-uniform surface, as described in Reference Example 9. These tables also show the adhesion to a uniform stainless steel (SUS) surface after UV irradiation curing, as described in Reference Example 10.
[0158] Table 2 - Comparative Examples 1-11 (Comp. 1-Comp. 11)
[0159]
[0160]
[0161] Table 3 - Comparative Example 12 (Comp. 12) and Working Examples 1-8 (Inv. 1 to Inv. 8)
[0162]
[0163] Table 4 - Working Examples 9-16 (Inv. 9 to Inv. 16)
[0164]
[0165] Table 5 - Working Examples 17-23 (Inv. 17 to Inv. 23)
[0166]
[0167]
[0168]
[0169] Table 6 - Change in Adhesion for Comparative Examples 2 and 4 and Working Examples 1, 9, 18, 20 and 21.
[0170]
[0171] Comparative Examples 1-5 show the impact of not using any (meth)acryloxyalkyl functional siloxane in the pressure sensitive adhesive composition. Comparative Examples 1, 2, 4 and 5 failed to adhere to uneven surfaces or had voids. Comparative Example 3 shows that the pressure sensitive adhesive cannot have sufficient crosslink density as shown by cohesive failure on the stainless steel (uniform) surface, although the pressure sensitive adhesive was laminated without voids; cohesive failure shows that after removing the tape, the pressure sensitive adhesive was torn and remained on the surface.
[0172] Comparative Examples 6 and 9 show that if the SiH / Vi ratio is too low (<0.2), the adhesion of the sample cannot be measured because insufficient crosslinking on the base film causes the pressure-sensitive adhesive prepared in Reference Example 10 to flow or be torn when the film with the fluorine-containing coating is removed. Comparative Examples 7, 8, 10 and 11 show that when the SiH / reactive group ratio is too high (>0.34), the sample cannot adhere to the uneven surface or has voids. Working Examples 1 and 2 with different SiH / Vi ratios and SiH / reactive group ratios (which contain the same starting materials as Comparative Examples 6 and 7) show that when the SiH / Vi ratio is 0.845 and 0.554 and the SiH / reactive group ratio is 0.331 and 0.217, the silicone hybrid pressure-sensitive adhesive without voids when laminated to the uneven surface can be prepared by laminating at 90°C for 30 minutes and then irradiating with UV under the conditions described in Reference Example 11. After UV irradiation, further crosslinking reaction occurs, so adhesion can be measured without cohesive failure, which is a performance that is significantly different from Comparative Example 3. Working Examples 1 and 2 show reprocessable properties with no remaining residue on the surface after UV irradiation.
[0173] Comparative Example 8 shows that when the SiH / reactive group ratio is 0.423 (>0.34), the sample cannot adhere to uneven surfaces or has voids. In contrast, working examples 3 and 4 with the same starting material show that when the SiH / reactive group ratio is 0.317 and 0.183, respectively, a silicone hybrid pressure-sensitive adhesive with no voids when laminated to an uneven surface can be prepared by laminating at 90°C for 30 minutes and then irradiating with UV under the conditions described in Reference Example 11. When working example 4 has a lower SiH / reactive group ratio than working example 3, the sample is laminated at RT for 30 minutes without heating without voids and then irradiated with UV. After UV irradiation, further crosslinking reactions occur, so adhesion can be measured without cohesive failure.
[0174] Comparative Examples 10 and 11 show that when the SiH / reactive group ratio is 0.401 and 0.604, respectively, the sample cannot adhere to the uneven surface or has voids. In contrast, when the SiH / reactive group ratio is 0.110 to 0.279, working examples 5 to 11 with the same starting material show that a silicone hybrid pressure-sensitive adhesive without voids when laminated to an uneven surface can be prepared by laminating at 90°C for 30 minutes and then irradiating with UV under the conditions described in Reference Example 11. In addition, working examples 14 to 20 with different amounts of crosslinking agent (C-2) show that when the SiH / Vi ratio is 0.331 and 0.597 and the SiH / reactive group ratio is 0.176 and 0.262, a silicone hybrid pressure-sensitive adhesive without voids when laminated to an uneven surface can be prepared by laminating at 90°C for 30 minutes and then irradiating with UV under the conditions described in Reference Example 9.
[0175] Working Examples 2, 4, 6, 8-12 and 17-20 show that when the SiH / reactive group ratio is 0.111 to 0.223, the samples are successfully laminated on uneven surfaces at RT without heating. Working Examples 1, 3, 5, 7, 14-16 have slightly higher crosslink density and show that when the SiH / reactive group ratio is 0.25 to 0.40, applying heat during lamination, such as 90°C, helps lamination on uneven surfaces without voids.
[0176] Working Examples 19, 21 and 22 show that when the SiH / Vi ratio is 0.241 to 0.331 and the SiH / reactive group ratio is 0.176 to 0.216, the samples are laminated on the uneven surface without voids. However, when the (m+o) / n ratio is 521 / 1, Comparative Example 12 using the starting material (A-5) shows cohesive failure even after UV irradiation, indicating that sufficient further crosslinking does not occur by UV irradiation under the test conditions. At the same time, Working Examples 19, 21 and 22 using starting materials (A-2 to A-5) with (m+o) / n ratios = 37 / 1 to 260 / 1 show 'adhesion failure' with no remaining residue on the surface after UV irradiation.
[0177] Optional starting materials such as (I) additives and (J) fillers which do not affect the crosslinking density when preparing the silicone hybrid pressure-sensitive adhesive layer may be used according to the needs of the industrial field, as shown in Working Examples 23 to 25.
[0178] Do not wish to be bound by theory, think that when laminated on uneven surface, SiH / Vi ratio and SiH / reactive group ratio represent the degree of crosslink density control, no matter how resin / polymer ratio, because resin / polymer ratio itself can not affect crosslink density.It is also believed that, because the factor of resin / polymer ratio is mainly related to adhesion characteristics, adhesion can be changed and lamination performance is maintained.For example, when resin / polymer ratio is 2.41 to 3.13, working examples Inv.5, 13 and 26 show relatively high adhesion and good lamination without gap, which shows that organic silicon hybrid pressure-sensitive adhesive composition can also be used for application field on the surface of needing high adhesion for long-term protection of electronic device.For some samples, heating during lamination helps to be laminated on uneven surface, as shown in Inv.7 and Inv.13.
[0179] Table 6 shows another advantage of the silicone hybrid pressure-sensitive adhesive for processing films. Conventional pressure-sensitive adhesives as per Comp. 2 and Comp. 4 show almost no change before and after UV irradiation. In particular, when exposed to high temperatures such as 125°C, the adhesion is highly increased, which means that the adhesion stability is poor and it is difficult to separate from the (opto)electronic device after processing. As shown in working examples 9, 18, 20, 21 in Table 6, the adhesion is reduced after UV irradiation and the low level of adhesion is maintained even after exposure to high temperatures.
[0180] Industrial Applicability
[0181] The organosilicon hybrid pressure-sensitive adhesive composition described herein can be cured to form an organosilicon hybrid pressure-sensitive adhesive. One object of this article is to provide a reactive deformable organosilicon hybrid pressure-sensitive adhesive that can be cured to a B-stage cure via hydrosilylation, for example, a reactive deformable organosilicon hybrid pressure-sensitive adhesive that is non-flowable at room temperature or elevated temperature and can be deformed by pressure, and can be formed into a desired shape, and can be further cured (C-stage cure) by light irradiation such as ultraviolet (UV) rays, but its shape is maintained. Another object is to provide control over the adhesion strength according to each application field that requires easy peeling or permanent bonding after UV irradiation. In addition, the organosilicon hybrid pressure-sensitive adhesive can also be used to protect certain areas of complex electronic components by conforming to uneven surfaces during device processing.
[0182] Use of terminology
[0183] Summary of the invention and description abstract are hereby incorporated by reference. Unless otherwise specified in the context of this specification, all amounts, ratios and percentages are by weight. Unless otherwise specified in the context of this specification, the articles "one", "a kind of" and "said" each refer to one (a kind) or more (multiple). The disclosure of a range includes the range itself and any values and endpoints contained therein. For example, the disclosure of a range>0.3 to 0.8 not only includes a range>0.3 to 0.8, but also includes 0.4, 0.55, 0.6, 0.7, 0.78 and 0.8 and any other number contained in the range individually. In addition, for example>0.3 to 0.8 The disclosure of the range includes, for example, 0.4 to 0.6, 0.35 to 0.78, 0.41 to 0.75, 0.78 to 0.8, 0.32 to 0.41, 0.35 to 0.5 subsets and any other subsets contained in the range. Similarly, the disclosure of a Markush group includes the entire group and also includes any individual members and subgroups contained therein. For example, the disclosure of the Markush group: vinyl, allyl, or hexenyl includes the individual member vinyl; the subgroups vinyl and hexenyl; and any other individual members and subgroups contained therein.
[0184] Abbreviations used in this application are as defined in Table 5 below.
[0185] Table 5
[0186]
[0187]
[0188] Test Method
[0189] [NMR analysis]
[0190] The average molecular formula of the starting materials (A) and (B) (such as those mentioned in Reference Examples 1 to 6) is based on the following 29 Si-NMR and 13 C-NMR analysis to determine:
[0191] NMR equipment: Fourier transform nuclear magnetic resonance spectrometer JEOL (JEOL is a registered trademark of JEOL Ltd., Japan) JNM-EX400 (product of JEOL Ltd.).
[0192] Determination method: Based on the various siloxane units derived from the following 29The average molecular formula is identified by finding the ratio of the integrated signal values obtained for the various siloxane units (M unit, D unit, T unit, and Q unit) and then finding the siloxane unit ratio based on the determined signal ratio. 28 Me2SiO in Si-NMR 2 / 2 Unit and MaMeSiO 2 / 2 The chemical shifts of the units overlap, so 13 C-NMR to determine the Me2SiO 2 / 2 (D) and MaMeSiO 2 / 2 The content of reactive groups including unsaturated bonds and (meth)acryloyl groups was obtained from the average molecular formula.
[0193] [SiH / Vi ratio and SiH / reactive group ratio]
[0194] The SiH / Vi ratio was calculated according to the following equation.
[0195]
[0196]
[0197] [Gel Permeation Chromatography]
[0198] Molecular weights were measured by gel permeation chromatography according to the following method; samples were prepared in toluene at 0.5% weight / volume concentration, filtered with a 0.45 μm PTFE syringe filter, and analyzed relative to polystyrene standards. The relative calibration (third order fit) for molecular weight determination was based on 16 polystyrene standards ranging from 580 Daltons to 2,610,000 Daltons. The chromatographic equipment consisted of a Waters 2695 separation module equipped with a vacuum degasser, a Waters 2414 differential refractometer, and two (7.8 mm×300 mm) styragel HR columns (molecular weight separation range of 100 to 4,000,000) preceded by a styragel guard column (4.6 mm×30 mm). Separations were performed using toluene programmed to flow at 1.0 mL / min, the injection volume was set to 100 μL, and the column and detector were heated to 45°C. Data were collected for 60 min and processed using Empower software. As used herein, for a resin, Mw (weight average molecular weight) and Mn (number average molecular weight) are
[0199] [Lamination test on uneven surfaces]
[0200] As described above in Example 11, the lamination performance on uneven surfaces was observed.
[0201] [Adhesion]
[0202] Adhesion was measured as described in Reference Example 12 above.
[0203] Embodiments of the present invention
[0204] In a first embodiment of the present invention, the silicone hybrid pressure-sensitive adhesive composition comprises:
[0205] 100 parts by weight of (A) a linear or substantially linear polydiorganosiloxane having reactive groups comprising silicon-bonded (meth)acryloxyalkyl functional groups in pendant positions and optionally silicon-bonded aliphatic unsaturated hydrocarbon groups in terminal positions, wherein the starting material (A) comprises units of formula M p M” q D m D' n D” o T'' r Q s ,in
[0206] M expression (R 1 3SiO 1 / 2 ),
[0207] M" expression (R 1 2R 3 SiO 1 / 2 ),
[0208] D expression (R 1 2SiO 2 / 2 ),
[0209] D' expression (R 1 R 2 SiO 2 / 2 ),
[0210] D" expression (R 1 R 3 SiO 2 / 2 ),
[0211] T"' expression (R 5 SiO 3 / 2 ) units, and
[0212] Q expression (SiO 4 / 2 ) units, where
[0213] Each R 1 is a monovalent hydrocarbon group containing no aliphatic unsaturated groups,
[0214] Each R2 is the (meth)acryloyloxyalkyl functional group,
[0215] each R 3 is the aliphatic unsaturated monovalent hydrocarbon group,
[0216] each R 5 is independently selected from R 1 , R 2 and R 3 ; and
[0217] the values of the subscripts p, q, m, n, o, r and s are such that:
[0218] 0 ≤ p, 0 ≤ q, 0 ≤ o, the amount (p + q) ≥ 2, the amount (q + o) ≥ 2,
[0219] 0 < m < 10,000, 2 < n ≤ 10,000, o ≥ 0, the amount (m + n + o) is from 100 to 10,000, the ratio (m + o) / n is from 1 / 1 to 500 / 1,
[0220] the ratio (q + o) / (m + n) is from 0 to ≤ 1 / 5,
[0221] 0 ≤ r ≤ 100, and
[0222] 0 ≤ s ≤ 100,
[0223] if 0 < r or if 0 < s, then the ratio (m + n + o) / (r + s) is from 50 / 1 to 10,000 / 1;
[0224] (B) a polyorganosilicate resin in an amount sufficient to provide a weight ratio of polyorganosilicate resin to (A) polydiorganosiloxane of 0.15 / 1 to 4 / 1 (resin / polymer ratio), wherein the polyorganosilicate resin comprises units of the formula M a M” b M”' c D d D' e T”' f Q h X i , where M”, D, D', T”' and Q are as described above, M”' represents a unit of the formula (R 1 2R 2 SiO 1 / 2 ) where R 1 and R 2 are as described above, X represents a hydroxyl group, and the values of the subscripts a, b, c, d, e, f, h and i are such that
[0225] a ≥ 0, b ≥ 0, c ≥ 0, and the amount (a + b + c) > 10 mol%;
[0226] d≥0, e≥0, and the amount (d+e) is from 0 to a value sufficient to provide 30 mole percent of combined D units and D' units to the resin;
[0227] f ≥ 0, provided that subscript f has a maximum value sufficient to provide 30 mol % of T"' units to the resin;
[0228] h>0, provided that subscript h has a value sufficient to provide 30 mol% to 60 mol% of Q units to the resin;
[0229] Amount (a+b+c+d+e+f+h) = 100 mol%;
[0230] i ≥ 0 is not included in the molar ratio, provided that the subscript i has a maximum value sufficient to provide 5 mole % of hydroxyl groups to the resin;
[0231] (C) a polyorganohydrogensiloxane comprising a unit formula M t M H u D v D H w T x T H y Q z , wherein M, D and Q represent units in the formula shown above, and
[0232] M H Expression (HR 1 2SiO 1 / 2 ),
[0233] D H Expression (HR 1 SiO 2 / 2 ),
[0234] T expression (R 1 SiO 3 / 2 ),
[0235] T H Expression (HSiO 3 / 2 ) units, and
[0236] the values of the subscripts t, u, v, w, x, y, and z are such that t≥0, u≥0, v≥0, w≥0, x≥0, y≥0, z≥0, the amount (u+w+y)≥3, and the amount (t+u+v+w+x+y+z) is sufficient to give the polyorganohydrogensiloxane a viscosity of 3 to 1,000 mPa·s at 25°C;
[0237] Provided that the starting materials (A), (B) and (C) and the amounts of each are sufficient to provide:
[0238] i) > 0.2 / 1 of the silicon-bonded hydrogen atoms in the starting material (C) and the aliphatic unsaturated monovalent hydrocarbon groups R in the starting material (A) and / or (B) 3 The molar ratio (SiH / Vi ratio),
[0239] ii) a molar ratio of silicon-bonded hydrogen atoms in the starting material (C) to reactive groups in the starting materials (A) and / or (B) (SiH / reactive group ratio) of <0.34, wherein the reactive groups are the combined R 2 and R 3 ;
[0240] (D) a hydrosilylation catalyst in an amount sufficient to provide 2 ppm to 500 ppm of platinum based on the combined weight of starting materials (A), (B) and (C);
[0241] 0.1 wt % to 10 wt % of (E) a photoradical initiator, based on the combined weight of starting materials (A), (B) and (C);
[0242] 10 ppm to 5,000 ppm of (F) a hydrosilylation reaction inhibitor, based on the combined weight of the starting materials (A), (B) and (C);
[0243] 5 ppm to 2,000 ppm of (G) a free radical scavenger, based on the combined weight of the starting materials (A) and (B);
[0244] 0 to 90 wt % of (H) a solvent, based on the combined amounts of all starting materials in the composition; and
[0245] 0 to 5 wt % of (I) an additive selected from sensitizers and synergists, based on the combined weight of the starting materials (A) and (B);
[0246] 0 to 30 wt % of (J) a filler selected from fumed silica or precipitated silica, based on the combined weight of the starting materials (A) and (B).
[0247] In a second embodiment, the starting material (A) in the composition of the first embodiment comprises a unit of formula M"2D m D' n , the amount (m+n) is 100 to 9,900, and the ratio m / n is 10 / 1 to 500 / 1.
[0248] In a third embodiment, the starting material (A) in the composition of the second embodiment has an amount (m+n)=200 to 9,900.
[0249] In a fourth embodiment, the starting material (A) in the composition of the third embodiment has an amount (m+n)=300 to 7,000.
[0250] In a fifth embodiment, the starting material (A) in the composition of any one of the second to fourth embodiments has a 1 , R 2 and R 3 R is present in a combined amount of 0.1 to 25 mol % 2 .
[0251] In a sixth embodiment, the starting material (A) in the composition of the fifth embodiment has R present in a mole % of 0.8% to 12%. 2 .
[0252] In a seventh embodiment, the starting material (A) in the composition of the sixth embodiment has R present at a mole % of 1.5% to 6%. 2 .
[0253] In an eighth embodiment, the starting material (B) in the composition of the seventh embodiment comprises a unit formula selected from the group consisting of: M a Q h 、M a M” b Q h 、M a M” b M"' c Q h 、M a M"' c Q h 、M a D d Q h 、M a D' e Q h 、M a M” b D' e Q h 、M a M” b T'' f Q h 、M a M” b T'' f Q h , wherein subscript a is 20 mol % to 65 mol %, subscripts b and c are 1 mol % to 30 mol %, subscripts d and e are 1 mol % to 20 mol %, subscript f is 1 mol % to 25 mol %, and subscript h is 35 mol % to 55 mol %.
[0254] In a ninth embodiment, in the starting materials (A) and (B) in any one of the first to eighth embodiments, each R 5 Independently selected from R 1 , R 2 and R 3 .
[0255] In a tenth embodiment, in the starting materials (A) and (B) of the ninth embodiment, R 5 For R 1 .
[0256] In an eleventh embodiment, the starting material (C) in any one of the first to tenth embodiments comprises units of formula M t M H u D v D H w , where the quantity (t+u)=2, and the quantity (u+w)≥3.
[0257] In a twelfth embodiment, in the composition of any one of the first to eleventh embodiments, for R 1 Each monovalent hydrocarbon group of is independently selected from an alkyl group and an aryl group.
[0258] In a thirteenth embodiment, in the composition of the twelfth embodiment, the alkyl group is methyl and the aryl group is phenyl.
[0259] In the fourteenth embodiment, in the composition of the twelfth embodiment or the thirteenth embodiment, each R 1 An alkyl group.
[0260] In a fifteenth embodiment, in the composition of any one of the first to fourteenth embodiments, for R 2 Each (meth)acryloxyalkyl functional group of is independently selected from acryloxypropyl and methacryloxypropyl.
[0261] In the sixteenth embodiment, in the composition of any one of the first to fifteenth embodiments, for R 3 Each aliphatically unsaturated monovalent hydrocarbon group of is an independently selected alkenyl group.
[0262] In a seventeenth embodiment, in the composition of the sixteenth embodiment, the alkenyl group is selected from vinyl and hexenyl.
[0263] In an eighteenth embodiment, in the composition of any one of the first to seventeenth embodiments, the resin / polymer ratio is from 0.2 / 1 to 3 / 1.
[0264] In a nineteenth embodiment, the composition of the eighteenth embodiment has a resin / polymer ratio = 0.3 / 1 to 2.5 / 1.
[0265] In a twentieth embodiment, in the composition of any one of the first to nineteenth embodiments, the SiH / Vi ratio is 0.21 / 1 to 22.0 / 1.
[0266] In a twenty-first embodiment, the composition of the nineteenth embodiment has a SiH / Vi ratio of 0.23 / 1 to <12.5 / 1.
[0267] In a twenty-second embodiment, the composition of the twenty-first embodiment has a SiH / Vi ratio of 0.23 / 1 to 0.9 / 1.
[0268] In a twenty-third embodiment, in the composition of the first to twenty-second embodiments, the SiH / reactive group ratio is from 0.03 to 0.30.
[0269] In a twenty-fourth embodiment, in the composition of the twenty-third embodiment, the SiH / reactive group ratio is from 0.04 to 0.28.
[0270] In a twenty-fifth embodiment, the starting material (D) in the composition of any one of the first to twenty-fourth embodiments is selected from: i) platinum group metals, ii) compounds of said metals, iii) complexes of said metals or said compounds, v) complexes microencapsulated in a matrix or core-shell structure.
[0271] In a twenty-sixth embodiment, starting material (D) in the composition of the twenty-fifth embodiment is present in an amount sufficient to provide 10 ppm to 100 ppm of platinum group metal based on the combined weight of starting materials (A), (B) and (C).
[0272] In a twenty-seventh embodiment, the starting material (E) in the composition of any one of the first to twenty-sixth embodiments is selected from the group consisting of benzophenone, substituted benzophenone compounds, acetophenone, substituted acetophenone compounds, benzoin, alkyl esters of benzoin, xanthone, and substituted xanthone.
[0273] In a twenty-eighth embodiment, the starting material (E) in the composition of the twenty-seventh embodiment is a substituted acetophenone.
[0274] In a twenty-ninth embodiment, the starting material (E) in the composition of the twenty-eighth embodiment is 1-hydroxycyclohexyl phenyl ketone.
[0275] In a thirtieth embodiment, in the composition according to any one of the first to twenty-ninth embodiments, the starting material (E) is present in an amount of 1 to 5 weight percent.
[0276] In a thirty-first embodiment, the starting material (F) in the composition of any one of the first to thirtieth embodiments is present and is selected from the group consisting of alkynols, cycloalkenylsiloxanes, enyne compounds, triazoles, phosphines, thiols, hydrazines, amines, fumarates, maleates, nitriles, ethers, carbon monoxide, alcohols, and silylated alkynols.
[0277] In a thirty-second embodiment, in the composition of the thirty-first embodiment, the acetylenic alcohol is ethynylcyclohexanol.
[0278] In a thirty-third embodiment, in the composition of any one of the first to thirty-second embodiments, the starting material (F) is present in an amount of 20 ppm to 2,000 ppm.
[0279] In the thirty-fourth embodiment, the starting material (G) free radical scavenger is present in the composition of any one of the first to thirty-third embodiments and the free radical scavenger is selected from: alkynols, cycloalkenylsiloxanes, enyne compounds, triazoles, phosphines, thiols, hydrazines, amines, fumarates, maleates, nitriles, ethers, carbon monoxide, alcohols and silylated alkynols.
[0280] In a thirty-fifth embodiment, in the composition of the first to thirty-fourth embodiments, the free radical scavenger is selected from phenolic compounds, phenothiazines, and anaerobic inhibitors.
[0281] In a thirty-sixth embodiment, in the composition of the thirty-fifth embodiment, the free radical scavenger is a phenolic compound.
[0282] In a thirty-seventh embodiment, in the composition of any one of the first to thirty-sixth embodiments, the starting material (G) free radical scavenger is present in an amount of 10 ppm to 1,500 ppm.
[0283] In a thirty-eighth embodiment, in the composition of any one of the first to thirty-seventh embodiments, the starting material (H) solvent is present and is selected from aliphatic hydrocarbons and aromatic hydrocarbons.
[0284] In a thirty-ninth embodiment, in the composition of any one of the first to thirty-eighth embodiments, the starting material (H) solvent is present in an amount of >0 wt% to 60 wt%.
[0285] In the fortieth embodiment, in the composition of any one of the first to fortieth embodiments, the (I) additive is present in an amount of 0.05 wt % to 3 wt %.
[0286] In the forty-first embodiment, in the composition of any one of the first to fortieth embodiments, the starting material (J) filler is present in an amount of 1 to 30 weight percent based on the combined weight of starting materials (A) and (B).
[0287] In the forty-second embodiment, in the composition of any one of the first to forty-first embodiments, the starting material (K) bis-SiH-terminated polydiorganosiloxane is present in a weight ratio of starting material (K) to starting material (C) [(K) / (C) ratio] of 0.25 / 1 to 4 / 1.
[0288] In a forty-third embodiment, in the composition of any one of the first to forty-second embodiments, a filler is present and is selected from fumed silica, precipitated silica, and both fumed silica and precipitated silica.
[0289] In a forty-fourth embodiment, a method for preparing an adhesive article comprising a pressure-sensitive adhesive layer on a surface of a substrate comprises the steps of:
[0290] Optionally 1) treating the surface of the substrate;
[0291] 2) applying the silicone hybrid pressure-sensitive adhesive composition of any of the preceding embodiments onto a surface;
[0292] Optionally 3) removing all or a portion of the solvent, if present;
[0293] 4) The silicone hybrid pressure-sensitive adhesive composition is heated to form a silicone hybrid pressure-sensitive adhesive layer on the surface of the substrate.
[0294] In a forty-fifth embodiment, a method for adhering an adhesive article to an uneven surface comprises:
[0295] Optionally 1) treating the surface of the substrate;
[0296] 2) applying the silicone hybrid pressure-sensitive adhesive composition of any of the preceding embodiments onto a surface;
[0297] Optionally 3) removing all or a portion of the solvent, if present;
[0298] 4) heating the organosilicon hybrid pressure-sensitive adhesive composition to form an organosilicon hybrid pressure-sensitive adhesive layer on the surface of the substrate;
[0299] 5) applying the adhesive article to the uneven surface such that the silicone hybrid pressure-sensitive adhesive layer contacts the uneven surface opposite the substrate;
[0300] Optionally 6) applying heat and / or pressure to the adhesive article and the uneven surface; and
[0301] 7) exposing the silicone hybrid pressure-sensitive adhesive layer to UV radiation,
[0302] This allows the silicone hybrid pressure-sensitive adhesive layer to conform to uneven surfaces.
[0303] In the forty-sixth embodiment, the method of the forty-fifth embodiment further comprises forming a silicone hybrid pressure-sensitive adhesive composition by mixing starting materials before step 1).
[0304] In a forty-seventh embodiment, in the method of the forty-fifth embodiment or the forty-sixth embodiment, the non-uniform surface is all or a portion of a ball grid array.
Claims
1. An organosilicon hybrid pressure-sensitive adhesive composition, the organosilicon hybrid pressure-sensitive adhesive composition comprising: 100 parts by weight of a starting material (A) having reactive groups comprising silicon-bonded (meth)acryloyloxyalkyl functional groups in pendant positions and optionally silicon-bonded aliphatic unsaturated hydrocarbon groups in terminal positions, wherein the starting material (A) comprises units of formula M p M″ q D m D′ n D″ o T″′ r Q s ,in M expression (R 1 3SiO 1 / 2 ), M″ expression (R 1 2R 3 SiO 1 / 2 ), D expression (R 1 2SiO 2 / 2 ), D′ expression (R 1 R 2 SiO 2 / 2 ), D″ expression (R 1 R 3 SiO 2 / 2 ), T″′ expression (R 5 SiO 3 / 2 ) units, and Q expression (SiO 4 / 2 ) units, where Each R 1 is a monovalent hydrocarbon group containing no aliphatic unsaturated groups, Each R 2 is the (meth)acryloyloxyalkyl functional group, Each R 3 is the aliphatic unsaturated monovalent hydrocarbon group, Each R 5 Independently selected from R 1 , R 2 and R 3 ,and The values of the subscripts p, q, m, n, o, r, and s are such that: 0 ≤ p, 0 ≤ q, 0 ≤ o, the amount (p + q) ≥ 2, the amount (q + o) ≥ 2, 0 < m < 10,000, 2 < n ≤ 10,000, o ≥ 0, the amount (m + n + o) is from 100 to 10,000, the ratio (m + o) / n is from 1 / 1 to 500 / 1, The ratio (q + o) / (m + n) is from 0 to ≤ 1 / 5, 0 ≤ r ≤ 100, and 0≤s≤100, If 0 < r or if 0 < s, then the ratio (m + n + o) / (r + s) is from 50 / 1 to 10,000 / 1; A starting material (B) in an amount sufficient to provide a weight ratio of the starting material (B) to the starting material (A) of 0.15 / 1 to 4 / 1, wherein the starting material (B) comprises a unit formula M a M″ b M″′ c D d D′ e T″′ f Q h X i , wherein M″, D, D′, T and Q are as described above, M″′ represents the formula (R 1 2R 2 SiO 1 / 2 ) unit, where R 1 and R 2 As stated above, X represents a hydroxyl group and the values of the subscripts a, b, c, d, e, f, h and i are such that: a ≥ 0, b ≥ 0, c ≥ 0, and the amount (a + b + c) > 10 mol%; d ≥ 0, e ≥ 0, and the amount (d + e) is from 0 to a value sufficient to provide 30 mol% of the combined D units and D' units to the starting material (B); f ≥ 0, provided that the subscript f has a maximum value sufficient to provide 40 mol% of the T''' units to the starting material (B); h > 0, provided that the subscript h has a value sufficient to provide 30 mol% to 70 mol% of the Q units to the starting material (B); a + b + c + d + e + f + h = 100 mol%; i ≥ 0 is not included in the molar ratio, provided that the subscript i has a maximum value sufficient to provide 5 mol% of hydroxyl groups to the starting material (B); The starting material (C) comprises a unit formula M t M H u D v D H w T x T H y Q z , wherein M, D, T and Q represent units in the formula shown above, and M H Expression (HR 1 2SiO 1 / 2 ), D H Expression (HR 1 SiO 2 / 2 ), T expression (R 1 SiO 3 / 2 ), T H Expression (HSiO 3 / 2 ) units, and The values of the subscripts t, u, v, w, x, y, and z are such that t ≥ 0, u ≥ 0, v ≥ 0, w ≥ 0, x ≥ 0, y ≥ 0, z ≥ 0, the amount (u + w + y) ≥ 2, and the amount (t + u + v + w + x + y + z) is sufficient to give the starting material (C) a viscosity of 3 mPa·s to 1,000 mPa·s at 25°C; Provided that the starting materials (A), (B), and (C) and their respective amounts are sufficient to provide: i) >0.2 / 1 of the silicon-bonded hydrogen atoms in the starting material (C) and the aliphatic unsaturated monovalent hydrocarbon groups R in the starting material (A) and / or (B) 3 The molar ratio of ii) a molar ratio of silicon-bonded hydrogen atoms in the starting material (C) to reactive groups in the starting materials (A) and / or (B) of <0.34, wherein the reactive groups are the combined R 2 and R 3 ; (D) A hydrosilylation catalyst, in an amount sufficient to provide 2 ppm to 500 ppm of platinum based on the combined weight of the starting materials (A), (B), and (C); Based on the combined weight of the starting materials (A), (B), and (C), 0.1 wt% to 10 wt% of (E) A photoinitiator; Based on the combined weight of the starting materials (A), (B), and (C), 10 ppm to 5,000 ppm of (F) a hydrosilylation inhibitor; Based on the combined weight of the starting materials (A) and (B), 5 ppm to 2,000 ppm of (G) a radical scavenger; Based on the combined amount of all starting materials in the composition, 0 wt% to 90 wt% of (H) a solvent; Based on the combined weight of the starting materials (A) and (B), 0 wt% to 5 wt% of (I) an additive selected from sensitizers and synergists; and Based on the combined weight of the starting materials (A) and (B), 0 wt% to 30 wt% of (J) a filler selected from fumed silica or precipitated silica.
2. The composition according to claim 1, wherein the starting material (A) comprises a unit formula M"2D m D' n , the amount (m+n) is 100 to 9,900, and the ratio m / n is 10 / 1 to 500 / 1.
3. The composition according to claim 1, wherein the starting material (B) comprises a unit formula selected from the group consisting of: M a Q h , U a M″ b Q h 、M a M″ b M″′ c Q h 、M a M″′ c Q h 、M a D d Q h , U a D′ e Q h 、M a M″ b D′ e Q h 、M a M″ b T″′ f Q h 、M a M″ b T″′ f Q h , wherein subscripts a, b and c are 20 mol % to 70 mol %, subscripts d and e are 1 mol % to 20 mol %, subscript f is 1 mol % to 25 mol %, and subscript h is 35 mol % to 65 mol %.
4. The composition according to claim 1, wherein the starting material (C) comprises a unit formula M t M H u D v D H w , where the quantity (t+u)=2, and the quantity (u+w)≥3.
5. The composition according to claim 1, wherein the weight ratio of the starting material (B) to the starting material (A) is from 0.2 / 1 to 3 / 1.
6. The composition according to claim 1, wherein (D) the hydrosilylation reaction catalyst is selected from: i) platinum group metals, ii) compounds of the metals, iii) complexes of the metals or the compounds, and v) the complexes microencapsulated in a matrix or core-shell structure.
7. The composition according to claim 1, wherein (E) the photo radical initiator is selected from the group consisting of benzophenone, substituted benzophenone compounds, acetophenone, substituted acetophenone compounds, benzoin, alkyl esters of benzoin, xanthone and substituted xanthone.
8. The composition of claim 1, wherein (F) the hydrosilylation reaction inhibitor is present and is selected from the group consisting of cycloalkenylsiloxanes, enyne compounds, triazoles, phosphines, thiols, hydrazines, amines, fumarates, maleates, nitriles, ethers, carbon monoxide, and alcohols.
9. The composition of claim 1, wherein the free radical scavenger is present and is selected from the group consisting of phenolic compounds, phenothiazines, and anaerobic inhibitors.
10. The composition of claim 1, wherein (H) the solvent is present and is selected from aliphatic hydrocarbons and aromatic hydrocarbons.
11. A method for preparing an adhesive article comprising a pressure-sensitive adhesive layer on a surface of a substrate, wherein the method comprises: Optionally 1) treating the surface of the substrate; 2) applying the organosilicon hybrid pressure-sensitive adhesive composition according to any one of claims 1 to 10 on the surface; Optionally 3) removing all or a portion of (H) the solvent, if present; 4) heating the silicone hybrid pressure-sensitive adhesive composition to form a silicone hybrid pressure-sensitive adhesive layer on the surface of the substrate.
12. The method according to claim 11, further comprising: 5) applying the adhesive article to an uneven surface such that the silicone hybrid pressure-sensitive adhesive layer contacts the uneven surface opposite the substrate; Optionally 6) applying heat and / or pressure to the adhesive article and the uneven surface; as well as 7) exposing the silicone hybrid pressure-sensitive adhesive layer to UV radiation, The silicone hybrid pressure-sensitive adhesive layer is thereby conformed to the uneven surface.
13. The method of claim 12, wherein the non-uniform surface is all or a portion of a ball grid array.
14. The composition of any one of claims 1 to 9, wherein in the starting material (B), the maximum value of subscript f is sufficient to provide 30 mol% of T"' units to the starting material (B), and the value of subscript h is sufficient to provide 30 mol% to 60 mol% of Q units to the starting material (B).
15. The composition according to claim 1 or claim 2, wherein the starting material (B) comprises a unit formula selected from the group consisting of: M a Q h 、M a M″ b Q h 、M a M″ b M″′ c Q h 、M a M″′ c Q h 、M a D d Q h 、M a D′ e Q h 、M a M″ b D′ e Q h 、M a M″ b T″′ f Q h 、M a M″ b T″′ f Q h ,in Subscript a is 20 mol % to 65 mol %, subscripts b and c are 1 mol % to 30 mol %, subscripts d and e are 1 mol % to 20 mol %, subscript f is 1 mol % to 25 mol %, and subscript h is 35 mol % to 55 mol %.
Citation Information
Patent Citations
Method for preparing a particulate material comprising a platinum-containing hydrosilylation catalyst and a silicone resin.
EP0347895A2
Micro assembled LED displays and lighting elements
US10985143B2
Pressure-sensitive adhesive sheet for optical member adhesion
US20130115450A1
Micro assembled LED displays and lighting elements
US20190148598A1
Copolymeric siloxanes and methods of preparing them
US2676182A